Porous film, organic optoelectronic element, and method for producing porous film

By using organic semiconductors as nanoporous films of forming materials in organic optoelectronic components, the problems of low external quantum efficiency and reduced color purity are solved, and more efficient light extraction and higher color purity are achieved.

CN114600264BInactive Publication Date: 2025-02-25YAMAGATA UNIVERSITY +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080074556.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-25
Filing Date
2020-10-22
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The external quantum efficiency of existing organic optoelectronic components is low, and light scattering leads to a decrease in color purity, making it difficult to apply to displays.

Method used

The nanoporous film using an organic semiconductor as the forming material has a crystal plane spacing d value obtained by X-ray scattering method ranging from 5 to 100 nm and a porosity of 20 to 80 volume %. In the manufacturing method, the vapor deposition process and the removal process are formed. Porous membrane.

Benefits of technology

The external quantum efficiency of organic optoelectronic components is improved, light scattering is reduced, and color purity is improved, making the components more suitable for use in displays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114600264B_ABST
    Figure CN114600264B_ABST
Patent Text Reader

Abstract

A porous film is provided which is formed of an organic semiconductor and has a lower refractive index than the organic semiconductor. In addition, an organic optoelectronic element having such a porous film is provided. In addition, a method for manufacturing a porous film which can easily manufacture such a porous film is provided. A porous film is formed of an organic semiconductor and has a plurality of continuous pores extending in the film thickness direction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a porous film, an organic optoelectronic element and a method for producing the porous film. Background Art

[0002] Conventionally, organic optoelectronic devices (organic electroluminescent devices, hereinafter referred to as organic EL devices) are known as self-luminous devices. Organic EL devices have a basic structure in which multiple layers such as a light-emitting layer, an electron transport layer, and a hole transport layer are stacked between a pair of electrodes.

[0003] Organic EL elements generate photons and emit light by recombination of electrons and holes supplied by power in the internal light-emitting layer. In the field of organic EL elements, through years of research and development, the ratio of "photons generated inside the element" to "number of injected electrons", i.e. "internal quantum efficiency", has reached nearly 100%.

[0004] On the other hand, in recent organic EL devices, the ratio of “photons extracted to the outside of the device” to “the number of electrons injected”, namely “external quantum efficiency”, is only about 20 to 30%, and improvement is required.

[0005] As one of the reasons for the low external quantum efficiency, internal reflection caused by the difference in refractive index of each layer constituting the organic EL element is considered. As mentioned above, the organic EL element has multiple layers in addition to the light-emitting layer. These layers have different refractive indices. Therefore, it is believed that the light generated by the light-emitting layer is reflected at the interface between the layers with different refractive indices, and is attenuated or absorbed inside the element before being emitted to the outside of the element.

[0006] In contrast, a light-emitting device is known in which a porous film is disposed above an anode or a cathode (see Patent Document 1). The light-emitting device described in Patent Document 1 is expected to improve light extraction efficiency by utilizing light scattering by the porous film.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application No. 2014-508385 Summary of the invention

[0010] Problem that the invention aims to solve

[0011] However, in view of the market demand for low power consumption and long life of components, the higher the external quantum efficiency of organic EL components, the better. In this regard, the external quantum efficiency of the light-emitting device described in Patent Document 1 has room for improvement. In addition, for the light extracted by the light-emitting device described in Patent Document 1, due to light scattering, light of various wavelengths is easily mixed, and the color purity is easily reduced. Therefore, the light-emitting device described in Patent Document 1 has the problem of being difficult to apply to displays.

[0012] The present invention is made in view of such a situation, and its object is to provide a porous film with an organic semiconductor as a formation material and a refractive index lower than that of the organic semiconductor. In addition, an organic optoelectronic element with such a porous film is provided. In addition, an object is to provide a method for manufacturing a porous film that can easily manufacture such a porous film.

[0013] Solutions for solving problems

[0014] In order to solve the above problems, the present invention includes the following aspects.

[0015] [1] A porous film formed of an organic semiconductor, the porous film having a plurality of continuous pores extending in a film thickness direction.

[0016] [2] The porous film according to [1], wherein the molecular weight of the organic semiconductor is 300 to 1,000.

[0017] [3] The porous film according to [1] or [2], wherein the interplanar spacing d value obtained by X-ray scattering is 5 to 100 nm.

[0018] [4] The porous film according to any one of [1] to [3], wherein the porosity is 20 to 80% by volume.

[0019] [5] The porous film according to any one of [1] to [4], further comprising a dopant for the organic semiconductor.

[0020] [6] An organic optoelectronic element comprising: a substrate; an anode disposed on the substrate; a cathode opposite to the anode; an active layer disposed between the anode and the cathode; a hole transport layer disposed between the active layer and the anode; and an electron transport layer disposed between the active layer and the cathode, wherein at least one layer selected from the group consisting of the active layer, the hole transport layer, and the electron transport layer is a porous membrane as described in any one of [1] to [5].

[0021] [7] A method for producing a porous membrane, comprising: a vapor deposition step of co-vapor depositing a fluorinated polymer and an organic semiconductor that are soluble in a fluorinated solvent to form a membrane; and a removal step of removing the fluorinated polymer contained in the membrane, wherein in the vapor deposition step, the ratio of the fluorinated polymer to the total of the fluorinated polymer and the organic semiconductor is 20 to 80% by volume, and in the removal step, a fluorinated solvent that dissolves the fluorinated polymer but does not substantially dissolve the organic semiconductor is used, and the fluorinated polymer contained in the membrane is dissolved in the fluorinated solvent and removed, thereby forming a plurality of continuous pores extending in the thickness direction of the membrane.

[0022] [8] The method for producing a porous film according to [7], wherein the molecular weight of the organic semiconductor is 300 to 1,000.

[0023] [9] The method for producing a porous film according to [7] or [8], wherein in the vapor deposition step, a dopant for the organic semiconductor is co-deposited together with the fluorinated polymer and the organic semiconductor.

[0024]

[10] The method for producing a porous film according to any one of [7] to [9], wherein the weight average molecular weight of the fluorinated polymer is 1,500 to 50,000.

[0025]

[11] The method for producing a porous film according to any one of [7] to

[10] , wherein the threshold temperature of the fluorinated polymer determined under the following conditions is 340° C. or less.

[0026] (Measurement conditions)

[0027] For fluoropolymers, the edge is 1×10 -3 When heating at a temperature of 2°C per minute under a vacuum of Pa, the evaporation rate is reduced from less than 0.1 g / (m 2 ·seconds) becomes 0.1g / (m 2 The boundary temperature above 100 0.1 0.1 0.2 0.4 0.6 0.8 0.9 0.1 0.2 0.4 ...4 0.8 0.9 0.1 0.4 0.

[0028]

[12] The method for producing a porous film according to any one of [7] to

[11] , wherein the fluorinated polymer is a perfluoropolymer having an aliphatic ring structure in its main chain.

[0029]

[13] The method for producing a porous film according to any one of [7] to

[11] , wherein the fluorinated polymer is a polymer having no aliphatic ring structure in the main chain and having a perfluoroalkyl group in the side chain.

[0030]

[14] The method for producing a porous film according to any one of [7] to

[13] , wherein the fluorine-containing solvent has a fluorine affinity parameter P calculated by the following method:F is 1 or more.

[0031] (Fluorophilic parameter P F )

[0032] In a two-phase system of 3 g toluene and 3 g perfluoromethylcyclohexane, 30 μL of the fluorinated solvent was added dropwise and mixed, and after standing overnight, the fluorinated solvent contained in the toluene and the fluorinated solvent contained in the perfluoromethylcyclohexane were measured by gas chromatography. The concentration of the fluorinated solvent in the toluene (unit: mL / L) was set to M P , let the concentration of the fluorinated solvent in the perfluoromethylcyclohexane (unit: mL / L) be M F When the value obtained by the following formula (A) is taken as the fluorine affinity parameter P F .

[0033] P F =M F / M P …(A)

[0034]

[15] The method for producing a porous membrane according to any one of [7] to

[14] , wherein in the removing step, the membrane is immersed in the fluorine-containing solvent.

[0035]

[16] The method for producing a porous film according to any one of [7] to

[14] , wherein in the removing step, the film is exposed to the vapor of the fluorine-containing solvent.

[0036]

[17] A method for manufacturing a porous membrane according to any one of [7] to

[16] , wherein a plurality of the aforementioned organic semiconductors are used, and in the aforementioned vapor deposition step, the aforementioned fluorinated polymer and a first organic semiconductor are co-vapor deposited to form a first film, and then the aforementioned fluorinated polymer and a second organic semiconductor are co-vapor deposited to form a second film, and in the aforementioned removal step, the aforementioned fluorinated polymer contained in the aforementioned first film and the aforementioned fluorinated polymer contained in the aforementioned second film are removed.

[0037]

[18] The method for producing a porous film according to any one of [7] to

[17] , further comprising, after the removal step, a step of vapor depositing the organic semiconductor to block the openings of the plurality of continuous pores.

[0038] Effects of the Invention

[0039] According to the present invention, a nanoporous film having an organic semiconductor as a formation material and a refractive index lower than that of an organic semiconductor can be provided. In addition, an organic optoelectronic element having such a nanoporous film can be provided. In addition, a method for manufacturing a nanoporous film that can easily manufacture such a nanoporous film can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a schematic perspective view showing the porous membrane according to the first embodiment.

[0041] Figure 2 is a schematic diagram showing an example of a scattering pattern of GI-SAXS.

[0042] Figure 3 This is an electron microscope photograph showing an example of the porous membrane according to the first embodiment.

[0043] Figure 4 It is a schematic diagram showing the process of manufacturing the porous membrane 1.

[0044] Figure 5 It is a schematic diagram showing the process of manufacturing the porous membrane 1.

[0045] Figure 6 It is a schematic diagram showing the process of manufacturing the porous membrane 1.

[0046] Figure 7 It is a schematic diagram showing the process of manufacturing the porous membrane 1.

[0047] Figure 8 It is an explanatory diagram of the method for producing the porous membrane 2 according to the second embodiment.

[0048] Fig. 9 It is an explanatory diagram of the method for producing the porous membrane 2 according to the second embodiment.

[0049] Fig.10 It is an explanatory diagram of the method for producing the porous membrane 2 according to the second embodiment.

[0050] Fig.11 It is an explanatory diagram of the method for producing the porous membrane 3 according to the third embodiment.

[0051] Fig.12 It is an explanatory diagram of the method for producing the porous membrane 3 according to the third embodiment.

[0052] Fig.13 1 is a schematic cross-sectional view showing an organic optoelectronic device (organic EL device) 100 according to a fourth embodiment.

[0053] Fig.14 It is an explanatory diagram of an organic EL element 200 according to the fifth embodiment.

[0054] Fig.15 This is a cross-sectional TEM image of the co-evaporated film produced in Example 1-2. DETAILED DESCRIPTION

[0055] The meanings of the terms in the present invention are as follows.

[0056] The "unit" constituting a polymer refers to a part derived from one molecule of a monomer that exists in a polymer and constitutes the polymer. A unit produced by addition polymerization of a monomer having a carbon-carbon unsaturated double bond is a divalent unit generated by cleaving the unsaturated double bond. In addition, a unit obtained by chemically converting the structure of a certain unit after the polymer is formed is also referred to as a unit. Hereinafter, a unit derived from each monomer is sometimes referred to by adding the name "unit" to the monomer name.

[0057] The "reactive functional group" refers to a reactive group that can react between molecules of the fluorinated polymer (excluding free radical reactions) or react with other components blended with the fluorinated polymer (excluding free radical reactions) to form a bond when heated or the like.

[0058] "Aliphatic ring" refers to a ring structure that does not show aromaticity. Aliphatic rings can be saturated or unsaturated. Aliphatic rings refer not only to carbocyclic structures in which the ring skeleton consists only of carbon atoms, but also to heterocyclic structures in which the ring skeleton contains atoms (heteroatoms) other than carbon atoms. Examples of heteroatoms include oxygen atoms, nitrogen atoms, sulfur atoms, and the like.

[0059] The “external quantum efficiency” is a value represented by the following formula.

[0060] η EQE =γ×η S ×q×η out

[0061] η EQE : External quantum efficiency (%), γ: Charge balance, η S : probability of luminescent exciton formation (%), q: luminescent quantum yield (%), η out : Light extraction efficiency (%).

[0062] The "refractive index of the fluorinated polymer" is a value measured in accordance with JIS K7142.

[0063] [First embodiment]

[0064] Below, refer to Figure 1 to Figure 7 , the porous membrane and the method for producing the porous membrane according to the present embodiment are described. It should be noted that in all the following drawings, the dimensions, ratios, etc. of the components are appropriately different for easy viewing of the drawings.

[0065] Figure 1 Schematic perspective view of the porous membrane of this embodiment. Figure 1As shown, the porous membrane 1 of this embodiment is formed of an organic semiconductor and has a plurality of continuous pores 11 that are continuous in the film thickness direction. Such a porous membrane 1 has a lower refractive index than an organic semiconductor membrane having no continuous pores 11.

[0066] In addition, since the solid portion of the porous membrane 1 is continuous in the membrane thickness direction, electrical conductivity can be ensured despite the presence of the continuous pores 11 .

[0067] In addition, it is considered that the porous membrane 1 has anisotropic conductivity because the continuous pores 11 formed in the membrane thickness direction have different conductivity in the planar direction and in the membrane thickness direction.

[0068] The refractive indexes of the “porous film 1 ” and the “organic semiconductor film not having the continuous pores 11 ” can be measured using model samples formed on a silicon substrate.

[0069] Specifically, for the refractive index of the porous film 1, a multi-incident angle spectroscopic ellipsometer (JA Woollam company: M-2000U) is used to measure the film formed on the silicon substrate by changing the incident angle of light by 5 degrees at a time within the range of 45 to 75 degrees. At each angle, Ψ and Δ as ellipsometric parameters are measured at intervals of about 1.6 nm in the range of wavelengths of 450 to 800 nm. Using the obtained measurement data, the dielectric constant of the organic semiconductor is fitted and analyzed using the Cauchy model, and the refractive index of the film formed on the silicon substrate to light of a wavelength of 600 nm can be obtained.

[0070] As the organic semiconductor, a known substance can be used, and an appropriate material can be selected according to the function of a device including the porous membrane 1 of the present embodiment.

[0071] For example, organic semiconductors include hole injection materials constituting the hole injection layer of the organic EL element, electron injection materials constituting the electron injection layer, hole transport materials constituting the hole transport layer, electron transport materials constituting the electron transport layer, and host materials and guest materials constituting the light-emitting layer.

[0072] As the hole injection material, aromatic amine derivatives can be appropriately exemplified, and specific examples thereof include α-NPD, TAPC, PDA, TPD, and m-MTDATA described below, but the present invention is not limited to these.

[0073]

[0074] Examples of hole injection materials other than those described above include the following materials.

[0075] Semiconductor materials of metal oxides such as molybdenum oxide or tungsten oxide;

[0076] Organic metal complex materials such as copper phthalocyanine;

[0077] N,N'-diphenyl-N,N'-bis-[4-(phenyl-m-tolyl-amino)-phenyl]-biphenyl-4,4'-diamine (DNTPD), N,N'-di(1-naphthyl)-N,N'-diphenylbenzidine (NPB), 4,4',4"-tris(N,N-diphenylamino)triphenylamine (TDATA), dipyrazino[2,3-f:2',3'-h]quinoxaline-2,3,6,7,10,11-hexacarbonitrile (HAT-CN), 9,9',9"-triphenyl-9H,9'H,9"H-3,3':6',3"-tricarbazole (Tris-PCz), 4,4',4"-tris(N,N-2-naphthylphenylamino)triphenylamine (2-TNATA) and other aromatic amine materials;

[0078] Polymer semiconductor materials such as polyaniline / dodecylbenzene sulfonic acid (PANI / DBSA), poly(3,4-ethylenedioxythiophene) / poly(4-styrene sulfonate) (PEDOT / PSS), polyaniline camphor sulfonic acid (PANI / CSA), or polyaniline / poly(4-styrene sulfonate) (PANI / PSS);

[0079] Commercially available products include N-(diphenyl-4-yl)-9,9-dimethyl-N-(4-(9-phenyl-9H-carbazolyl-3-yl)phenyl)-9H-fluoren-2-amine (hereinafter referred to as "HT211"), HTM081 (manufactured by Merck), HTM163 (manufactured by Merck), HTM222 (manufactured by Merck), NHT-5 (manufactured by NoValed), NHT-18 (manufactured by NoValed), NHT-49 (manufactured by NoValed), NHT-51 (manufactured by NoValed), NDP-2 (manufactured by NoValed), and NDP-9 (manufactured by NoValed).

[0080] The hole injection materials exemplified can be purchased from the market. These hole injection materials can be commercial products or synthetic products. In addition, the above hole injection materials can be used alone or in combination of two or more.

[0081] As the electron injection material, known materials can be used. As specific examples, inorganic compounds such as LiF, Cs2CO3, CsF, the following Alq3, PBD, TAZ, BND, OXD-7, 8-hydroxyquinoline-lithium (Liq), etc. can be cited, but are not limited to these. In addition, commercial products such as NDN-1 (made by NoValed) and NDN-26 (made by NoValed) can also be used.

[0082]

[0083] Examples of the material of the hole transport layer (hole transport material) include the above-mentioned aromatic amine derivatives such as α-NPD, PDA, TAPC, TPD, and m-MTDATA, but are not limited thereto.

[0084] As other hole transport materials, there can be mentioned triazole derivatives, oxadiazole derivatives, imidazole derivatives, pyrazoline derivatives and pyrazolone derivatives, phenylenediamine derivatives, arylamine derivatives, amino-substituted chalcone derivatives, oxazole derivatives, styrylanthracene derivatives, fluorenone derivatives, hydrazone derivatives, stilbene derivatives, silazane derivatives, etc. Among them, porphyrin compounds, aromatic tertiary amine compounds and styrylamine compounds are preferably used, and aromatic tertiary amine compounds are particularly preferably used.

[0085] As other hole transport materials, the following materials can be mentioned.

[0086] DNTPD, NPB, TDATA, HAT-CN, 2-TNATA, Tris-PCz, 4,4',4"-tris(9-carbazolyl)triphenylamine (TCTA), 2,2',7,7'-tetrakis(N,N-diphenylamino)-2,7-diamino-9,9'-spirobifluorene (Spiro-TAD), 2,2',7,7'-tetrakis(N,N-di(p-methoxyphenyl)amino)-9,9'-spirobifluorene (Spiro-MeOTAD) and the like;

[0087] PANI / DBSA, PEDOT / PSS, or PANI / CSA, PANI / PSS and other aforementioned polymer semiconductor materials;

[0088] HT211, HTM081 (manufactured by Merck), HTM163 (manufactured by Merck), HTM222 (manufactured by Merck), NHT-5 (manufactured by NoValed), NHT-18 (manufactured by NoValed), NHT-49 (manufactured by NoValed), NHT-51 (manufactured by NoValed), NDP-2 (manufactured by NoValed), NDP-9 (manufactured by NoValed), etc., the aforementioned commercial products.

[0089] These hole transport materials may be commercially available products or synthetic products. The above hole transport materials may be used alone or in combination of two or more.

[0090] As the material of the electron transport layer (electron transport material), a known material can be used. For example, as the electron transport material, Alq3, PBD, TAZ, BND, OXD-7, 2,2',2"-(1,3,5-benzenetriyl)-tris(1-phenyl-1-H-benzimidazole) (TPBi), 8-hydroxyquinoline-lithium (Liq) and the like can be cited. In addition, as the electron transport material, BCP, t-Bu-PBD, and silole derivatives can also be cited.

[0091] These electron transport materials may be commercially available products or synthetic products. The electron transport materials may be used alone or in combination of two or more.

[0092] As a material for forming the light-emitting layer, a known material such as a fluorescent material, a thermally activated delayed fluorescence (TADF) material, or a phosphorescent material can be used.

[0093] For example, as the material for forming the light-emitting layer, there can be mentioned (E)-2-(2-(4-(dimethylamino)phenylvinyl)-6-methyl-4H-pyran-4-ylidene)malononitrile (DCM), 4-(dicyanomethylidene)-2-methyl-6-julolidyl-9-enyl-4H-pyran (DCM2), rubrene, coumarin 6 (Coumarin6), Ir(ppy)3, (ppy)2Ir(acac) and other light-emitting guest materials, 4,4'-bis(9H-carbazole-9-yl)biphenyl (CBP), 3,3'-bis(9H-carbazole-9-yl)-1,1'-biphenyl (mCBP) and other phosphorescent host materials, ADN, Alq3 and other fluorescent host materials, polyphenylene vinylene (PPV), MEH-PPV and other polymer materials, but it is not limited to these.

[0094] The material for forming the light-emitting layer may be used alone or in combination of two or more. The material for forming the light-emitting layer may be appropriately selected according to the desired light emission wavelength.

[0095] The molecular weight of the organic semiconductor as the material for forming the porous membrane 1 is preferably 300 to 1000. The molecular weight of the organic semiconductor is more preferably 400 or more. Furthermore, the molecular weight of the organic semiconductor is more preferably 900 or less.

[0096] When the molecular weight of the organic semiconductor is 300 or more, the glass transition point (Tg) of the organic semiconductor becomes higher and the heat resistance of the organic semiconductor film is improved. When the molecular weight is 1000 or less, the vapor pressure of the organic semiconductor becomes higher and deposition can be performed below the thermal decomposition temperature.

[0097] The upper limit and lower limit of the molecular weight of the organic semiconductor may be arbitrarily combined. That is, the molecular weight of the organic semiconductor may be 300 to 900, 400 to 1000, or 400 to 900.

[0098] The molecular weight of the organic semiconductor can be determined by measurement using TOF-SIMS (Time-of-Flight Secondary Ion Mass Spectrometry).

[0099] The porous membrane 1 is formed of an organic semiconductor and is continuous in the film thickness direction. Therefore, the porous membrane 1 has a charge transport capability. It should be noted that the "charges" that the porous membrane 1 can transport are holes or electrons.

[0100] The continuous pores 11 are continuous in the film thickness direction of the porous membrane 1 . Figure 1 In the embodiment, the continuous pores 11 penetrate the porous membrane 1 along the membrane thickness direction.

[0101] The porosity of the porous membrane 1 is preferably 20 to 80% by volume. When the porosity of the porous membrane 1 is 20% by volume or more, the refractive index of the porous membrane 1 is sufficiently low compared to an organic semiconductor membrane having no continuous pores 11. When the porosity of the porous membrane 1 is 80% by volume or less, the membrane strength of the porous membrane 1 can be sufficiently ensured.

[0102] The porosity of the porous membrane 1 can be appropriately set within the above range according to the required refractive index of the porous membrane 1 .

[0103] It should be noted that the porosity of the porous membrane 1 can be calculated by the following formula (B). In the following formula (B), the refractive index of air (n a ) is 1, and the refractive index of the organic semiconductor and the porous film is the value determined by the above-mentioned measurement method.

[0104] Porosity (%) = (n p -n o ) / (n a -n o )×100…(B)

[0105] n p : Refractive index of porous membrane

[0106] n o : Refractive index of organic semiconductor

[0107] n a : Refractive index of air

[0108] The interplanar spacing d value obtained by the X-ray scattering method for the porous membrane 1 is preferably 5 to 100 nm, more preferably 5 to 60 nm. The above-mentioned d value is a value corresponding to the distance between adjacent continuous holes 11. The larger the d value, the farther the adjacent continuous holes 11 are, and the smaller the d value, the closer the adjacent continuous holes 11 are. When the d value is within the above range, visible light can be transmitted through the porous membrane 1 without scattering.

[0109] The d value is a value obtained by performing cluster structure evaluation based on small-angle X-ray scattering (SAXS).

[0110] Specifically, the incident X-rays were firstly generated using the Aichi synchrotron BL8S3 with a wavelength of (8.2keV), the beam size was set to about 850μm×280μm, the camera length was set to 1121.52mm, the detector used was R-AXISIV (imaging plate), the exposure time was set to 60 seconds, and the X-ray scattering diffraction was measured by the small-angle X-ray scattering method.

[0111] The obtained data was processed by circular averaging of the two-dimensional data using Fit 2D software, and then converted to one dimension. The background correction, transmittance correction, and air scattering correction during IP reading were performed to obtain the d value. The sample thickness correction was omitted due to low accuracy and uneven locations.

[0112] It should be noted that the measurement conditions of the d value are not limited to the above method, and other measurement conditions may be used as long as the d value can be appropriately measured.

[0113] In the porous membrane 1, the plurality of continuous pores 11 are preferably formed in the thickness direction of the porous membrane 1 (oriented in the thickness direction). In the following description, the property that the plurality of continuous pores 11 are formed in the thickness direction of the porous membrane 1 may be referred to as "vertical orientation".

[0114] The vertical orientation of the continuous pores 11 as described above can be evaluated by grazing incidence small angle X-ray scattering (GI-SAXS).

[0115] For example, the porous membrane 1 can be evaluated using BL-6A of a high energy accelerator research institute. The wavelength of the incident X-ray is set to The incident angle was set to 0.16° with respect to the direction parallel to the surface of the porous membrane 1, the detector was PILATUS3 1M, and the camera length was set to 2.5 m. The measurement conditions are not limited to these, and any conditions may be used as long as the orientation can be appropriately evaluated.

[0116] Generally, when a sample whose microstructure is not oriented in a predetermined direction is irradiated with X-rays, isotropic scattering of the X-rays is obtained. On the other hand, when a sample whose microstructure is oriented is irradiated with X-rays, the scattered X-rays reflect the orientation state of the microstructure and produce regularity in the scattering direction, and the scattered lights interfere with each other, resulting in the observation of locally strong scattered light.

[0117] Figure 2 is a schematic diagram showing an example of a scattering pattern in GI-SAXS.

[0118] In GI-SAXS, the direction of the orthogonal projection vector of the incident X-ray relative to the sample surface is q x direction, and the direction parallel to the sample surface and perpendicular to the qx direction is defined as q y direction, and the normal direction of the sample surface is set to q z direction.

[0119] Figure 2 for q y q z X-ray scattering pattern of a plane.

[0120] Figure 2 (a) is a model of a scattering pattern when a film (sample) having a microstructure oriented in the film thickness direction or a phase separation structure is evaluated by GI-SAXS.

[0121] Figure 2 (b) is a model of a scattering pattern when a film (sample) having a microstructure or a phase-separated structure oriented in a direction parallel to the film surface is evaluated by GI-SAXS.

[0122] Figure 2 (c) is a model of a scattering pattern when a film (sample) without orientation in a microstructure is evaluated by GI-SAXS.

[0123] Figure 2 In q z The signal with the strongest intensity rising in the direction corresponds to the X-rays obtained by specular reflection of the incident X-rays on the sample surface. In the following description, the signal of "the X-rays obtained by specular reflection of the incident X-rays on the sample surface" is referred to as "main signal X".

[0124] In this embodiment, if Figure 2 As shown in the scattering pattern (a), the main signal X is ±q y The position detected at q z In the case of a strong signal a with a rising direction, it is determined that the microstructure is oriented in the vertical direction.

[0125] In addition, if Figure 2As shown in (b) of the scattering pattern, when the intersection with the main signal X is detected and the ±q y In the case of the signal b extending in the same direction, it is determined that the microstructures are oriented in a direction parallel to the film surface.

[0126] Furthermore, if Figure 2 When a signal c is detected that overlaps with the main signal X and continues in a semicircular shape, as in the scattering pattern shown in (c), it is determined that the scattering of X-rays is isotropic and there is no orientation in the microstructure.

[0127] For detailed comparison, q y Direction and q z The scattering intensity ratios in different directions are compared.

[0128] The diameter of the opening 11 a of the continuous pore 11 is preferably 5 to 100 nm. When the diameter of the opening 11 a of the continuous pore 11 is within this range, it is sufficiently small with respect to visible light, and thus the visible light incident on the porous membrane 1 is less likely to be scattered.

[0129] The porous membrane 1 may further contain a dopant for an organic semiconductor. A known dopant may be used as the dopant, and an appropriate material may be selected according to the function of a device including the porous membrane 1 of this embodiment. By containing a dopant, the porous membrane 1 can improve electrical conductivity.

[0130] For example, as a dopant for an organic semiconductor used as a hole injecting material, the following materials can be mentioned.

[0131] TCNQ, F4-TCNQ, PPDN, TCNNQ, F6-TCNNQ, HAT-CN, HATNA, HATNA-Cl6, HATNA-F6, C 60 F 36 、F 16 - Organic dopants such as CuPc, NDP-2 (manufactured by Novaled), and NDP-9 (manufactured by Novaled);

[0132] Inorganic dopants such as MoO3, V2O5, WO3, ReO3, CuI, etc.

[0133] Examples of the dopant used as the electron injection material include 8-hydroxyquinoline-lithium (Liq), NDN-1 (manufactured by Novaled), and NDN-26 (manufactured by Novaled).

[0134] Figure 3The electron microscope photograph of an example of the porous membrane of the present embodiment is an enlarged photograph taken by photographing the surface of the porous membrane. As shown in the figure, the openings of a plurality of continuous pores 11 can be confirmed on the surface of the porous membrane 1. The diameter of the continuous pores 11 of the porous membrane 1 shown in the figure is about 10 to 20 nm.

[0135] It should be noted that Figure 1 , Figure 3 In the embodiment, the continuous hole 11 penetrates the porous membrane 1, but is not limited thereto. For example, the opening at one end of the continuous hole 11 may be blocked by the material forming the porous membrane 1, or the openings at both ends of the continuous hole 11 may be blocked by the material forming the porous membrane 1. In addition, the openings at one end or both ends of the continuous hole 11 may be physically or thermally treated to break up the porous membrane 1 to block it, or the material forming the porous membrane 1 may be vapor-deposited on the porous membrane 1 to block it.

[0136] When at least one end side of the continuous pore 11 is blocked by the material forming the porous membrane 1 , the continuous pore 11 is continuously formed with a length of 50% or more relative to the film thickness of the porous membrane 1 .

[0137] Figures 4 to 7 It is a schematic diagram which shows the process of manufacturing the said porous membrane 1.

[0138] First, if Figure 4 As shown, a substrate 50 for forming a porous membrane 1 is prepared. Such a substrate 50 is placed in a chamber 500 of a vacuum evaporation device, and an organic semiconductor 51a and a fluorine-containing polymer 52a are supplied from an evaporation source (crucible) 51 of an organic semiconductor and an evaporation source (crucible) 52 of a fluorine-containing polymer to perform co-evaporation. It should be noted that Figure 4 In the figure, the organic semiconductor and the fluorine-containing polymer are vapor-deposited from separate vapor deposition sources, but they may be vapor-deposited from the same vapor deposition source.

[0139] In the co-evaporation, the vapor deposition conditions are set so that the ratio of the fluorinated polymer to the total of the fluorinated polymer and the organic semiconductor in the co-evaporated film formed on the substrate 50 becomes 20 to 80 volume %.

[0140] The organic semiconductor 51a may be a substance that is not decomposed by heating during vapor deposition. Whether the substance is not decomposed by heating during vapor deposition can be determined by calculating the weight loss rate of the organic semiconductor used in the following method.

[0141] (Judgment method)

[0142] The measurement was performed using a vacuum differential thermal balance (VPE-9000 manufactured by ADVANCE RIKO, Inc.). 50 mg of the organic semiconductor was placed in a sample cell with an inner diameter of 7 mm and the measurement was performed at 1×10-3 ~1×10 -4 The weight loss rate (%) of the organic semiconductor when the temperature is increased by 2°C per minute to 500°C under a vacuum degree of 1.5 Pa, and the temperature (T d50 ).

[0143] Next, a thermogravimetric differential thermal analyzer (STA7200 manufactured by Hitachi High-Tech Science Corporation) was used to measure the weight loss rate of the organic semiconductor when the temperature was raised to 450° C. at 10° C. per minute under a nitrogen flow to determine T d50 The weight loss rate.

[0144] T d50 When the weight loss rate under normal pressure is less than 1%, it is judged that the T under reduced pressure d50 The reason for the weight loss is not due to thermal decomposition but evaporation. It can be judged that such an organic semiconductor is a material that does not decompose under heating during vapor deposition, that is, it is suitable for vapor deposition.

[0145] On the other hand, T d50 If the weight loss rate under normal pressure exceeds 1%, it is judged that the T under reduced pressure d50 The reason for the weight loss is thermal decomposition. It is believed that such an organic semiconductor is decomposed by heating during vapor deposition and is therefore not suitable for vapor deposition.

[0146] The organic semiconductor 51a used for vapor deposition preferably has a molecular weight of 300 to 1,000.

[0147] (Fluoropolymer)

[0148] The fluorine-containing polymer 52a used in the method for producing the porous membrane of the present embodiment is a polymer containing fluorine atoms. It should be noted that in the present invention, oligomers are also included in polymers. That is, the fluorine-containing polymer may also be an oligomer.

[0149] The fluorine-containing polymer used in the method for producing the porous membrane of the present embodiment is a fluorine-containing polymer that is soluble in a fluorine-containing solvent. Whether the fluorine-containing polymer is soluble in a fluorine-containing solvent can be confirmed in advance by preliminary experiments. The fluorine-containing solvent used will be described later.

[0150] The solubility of the fluorinated polymer was determined by the following method.

[0151] 10 g of fluorinated polymer was added to 1000 g of fluorinated solvent, stirred at 25°C for 24 hours, and then filtered using a polytetrafluoroethylene (PTFE) filter with a nominal opening of 1 μm and a diameter of 47 mm. The filtered filter was vacuum dried at 50°C for 1 hour, and the mass of the dried filter was measured to determine the increase in mass relative to the filter before filtration. If the mass increase was 0.1 g or less, it was determined to be dissolved.

[0152] The fluorinated polymer preferably has an evaporation rate or saturated vapor pressure sufficient for vapor deposition at a temperature lower than the temperature at which the fluorinated polymer thermally decomposes. The thermal decomposition starting temperature of PTFE, a common fluorinated polymer, is about 400°C, and the thermal decomposition starting temperature of Teflon (registered trademark) AF is 350°C.

[0153] The fluorinated polymer used in the present embodiment preferably has a threshold temperature of 340° C. or less as determined under the following conditions. (Measurement Conditions)

[0154] For fluoropolymers, the edge is 1×10 -3 When heating is performed at a temperature increase of 2°C per minute under a vacuum degree of Pa, the evaporation rate is reduced from less than 0.1 g / (m 2 ·seconds) becomes 0.1g / (m 2 The boundary temperature above 100 0.1 0.1 0.2 0.4 0.6 0.8 0.9 0.1 0.2 0.4 ...4 0.8 0.9 0.1 0.4 0.

[0155] The saturated vapor pressure of the fluorinated polymer used in the present embodiment at 300° C. is preferably 0.001 Pa or more, more preferably 0.002 Pa or more.

[0156] From this viewpoint, perfluoropolymers are preferred as fluorine-containing polymers, which are believed to have small intermolecular interactions. In addition, polymers having aliphatic ring structures in the main chains described below, which have low crystallinity, are more preferred as fluorine-containing polymers.

[0157] In this specification, the evaporation rate and saturated vapor pressure (unit: Pa) are values ​​measured using a vacuum differential thermal balance (VAP-9000 manufactured by ADVANCERIKO, Inc.). Specifically, 50 mg of the fluorinated polymer was placed in a sample cell with an inner diameter of 7 mm and the sample was stirred at 1×10 -3 Pa vacuum, the temperature was raised at 2°C per minute, and the evaporation rate (unit: g / (m 2 · seconds)). The saturated vapor pressure is calculated using the evaporation rate and molecular weight.

[0158] The weight average molecular weight (hereinafter referred to as "Mw") of the fluorinated polymer is preferably from 1,000 to 50,000, more preferably from 1,500 to 40,000, further preferably from 2,000 to 30,000.

[0159] When the weight average molecular weight is 1,000 or more, the Tg of the fluorine-containing resin becomes high and the formed phase separation structure is less likely to collapse.

[0160] On the other hand, when the weight average molecular weight is 50,000 or less, it has a saturated vapor pressure that provides a practical layer formation speed (film formation speed), so it is not necessary to heat the evaporation source to a high temperature, specifically a temperature exceeding 400°C. If the temperature of the evaporation source is too high, the main chain of the fluorinated polymer will be cleaved during the evaporation process, the fluorinated polymer will be reduced in molecular weight, the strength of the formed layer will become insufficient, and defects from decomposition products will be generated, making it difficult to obtain a smooth surface. In addition, it is assumed that the molecules or ions generated by the cleavage of the main chain and accidentally mixed in may affect the conductivity of the film and the luminescence life of the organic EL element.

[0161] Therefore, when the Mw of the fluorinated polymer is in the range of 1,000 to 50,000, the main chain of the fluorinated polymer is not broken, and a layer having sufficient strength and a smooth surface can be formed.

[0162] The weight average molecular weight of the fluorinated polymer is a value measured using gel permeation chromatography (GPC). First, a PMMA standard sample with a known molecular weight is measured using GPC, and a calibration curve is prepared based on the dissolution time and molecular weight of the peak top. Next, the fluorinated polymer is measured, and Mw and Mn are obtained based on the calibration curve. The mobile phase solvent is a mixed solvent of 1,1,1,2,3,4,4,5,5,5-decafluoro-3-methoxy-2-(trifluoromethyl)pentane / hexafluoroisopropanol (85 / 15 by volume).

[0163] "Polydispersity" refers to the ratio of Mw to the number average molecular weight (hereinafter, represented by "Mn"), i.e., Mw / Mn. From the viewpoint of the stability of the quality of the formed layer, the polydispersity (molecular weight distribution) (Mw / Mn) of the fluorinated polymer is preferably small, preferably 2 or less. As the polydispersity of the fluorinated polymer, it is more preferably 1.5 or less, and further preferably 1.2 or less. It should be noted that the theoretical lower limit of the polydispersity is 1.

[0164] The smaller the polydispersity of the fluorinated polymer, the smaller the variation in the deposition conditions becomes, and it is easier to form a homogeneous phase separation structure in the film thickness direction.

[0165] As methods for obtaining fluorinated polymers with low polydispersity, there can be mentioned methods of controlled polymerization such as living free radical polymerization, molecular weight cutoff purification using size exclusion chromatography, molecular weight cutoff purification based on sublimation purification and supercritical extraction. Among these methods, sublimation purification is preferably performed in consideration of the stability of the evaporation rate when the evaporation method is applied to the formation of the layer.

[0166] In addition, in this specification, the weight average molecular weight and polydispersity are values ​​measured by gel permeation chromatography (GPC).

[0167] Fluorine-containing polymers with higher Tg are preferred because the formed phase separation structure is stable. Specifically, the Tg of the fluorine-containing polymer is preferably 30°C or higher, more preferably 50°C or higher, and particularly preferably 70°C or higher. The upper limit is not particularly limited, but is preferably 350°C, and more preferably 300°C.

[0168] The higher the Tg of the fluorinated polymer, the easier it is to form a stable phase separation structure.

[0169] In the case where the perfluoropolymer having a fluorinated aliphatic ring structure in the main chain is a perfluoropolymer formed only by units formed by cyclopolymerization of perfluoro(3-butenyl vinyl ether), its intrinsic viscosity [η] is preferably 0.01 to 0.14 dl / g, more preferably 0.02 to 0.1 dl / g, and particularly preferably 0.02 to 0.08 dl / g. When [η] is 0.01 dl / g or more, the molecular weight of the fluorinated polymer becomes relatively large, and the layer after co-evaporation is easy to obtain sufficient heat resistance. On the other hand, when [η] is 0.14 dl / g or less, the molecular weight of the fluorinated polymer becomes relatively small, and has a saturated vapor pressure that provides a practical film-forming speed.

[0170] In this specification, the intrinsic viscosity [η] (unit: dl / g) is a value measured at a measurement temperature of 30°C using ASAHIKLIN (registered trademark) AC2000 (manufactured by AGC Corporation) as a fluorinated solvent using an Ubbelohde type viscometer (manufactured by Shibata Scientific Co., Ltd.: Viscometer Ubbelohde).

[0171] Examples of the fluorinated polymer soluble in a fluorinated solvent include the following polymers (1) and (2).

[0172] Polymer (1): a fluorinated polymer having no aliphatic ring in the main chain and having a perfluoroalkyl group in the side chain;

[0173] Polymer (2): A fluorine-containing polymer having an aliphatic ring in its main chain.

[0174] 《Polymer (1)》

[0175] The phrase “having no ring structure in the main chain” means that the carbon atoms constituting the main chain of the fluorine-containing polymer are not carbon atoms constituting a ring skeleton.

[0176] Examples of polymers having no ring structure in the main chain include polymers formed by polymerization of a compound having one polymerizable double bond. In this case, the main chain of the polymer is a linear carbon chain formed by reaction (polymerization) of the polymerizable double bond.

[0177] As the perfluoroalkyl group in the side chain of the polymer (1), a linear or branched perfluoroalkyl group having 2 to 8 carbon atoms is preferred, and a perfluoroalkyl group having 4 to 6 carbon atoms is particularly preferred. When the number of carbon atoms of the perfluoroalkyl group is 2 or more, it is easily dissolved in a fluorinated solvent. When the number of carbon atoms is 8 or less, even if decomposition products are produced, adverse effects are unlikely to occur.

[0178] Examples of perfluoroalkyl groups include -(CF2)3CF3, -CF2CF(CF3)2, -C(CF3)3, -(CF2)4CF3, -(CF2)2CF(CF3)2, -CF2C(CF3)3, -CF(CF3)CF2CF2CF3, -(CF2)5CF3, -(CF2)3CF(CF3)2, etc., with -(CF2)3CF3 and -(CF2)5CF3 being particularly preferred.

[0179] Examples of the polymer (1) include a polymer having a unit derived from a monomer having one polymerizable double bond and having a perfluoroalkyl group at a terminal (hereinafter, also referred to as "monomer (f1)").

[0180] As monomer (f1), for example, 2-perfluorohexylethyl acrylate (hereinafter also referred to as "C6FA"), 2-perfluorohexylethyl methacrylate (hereinafter also referred to as "C6FMA"), 2-perfluorobutylethyl acrylate, 3,3,4,4,5,5,6,7,7,7-decafluoro-6-(trifluoromethyl)heptyl acrylate, 2-perfluorohexylethyl α-chloroacrylate) (hereinafter also referred to as "α-ClC6FA"), etc. can be mentioned.

[0181] The polymer (1) may be a homopolymer of the monomer (f1) or a copolymer of other monomers copolymerizable with the monomer (f1).

[0182] Examples of other monomers copolymerizable with the monomer (f1) include (meth)acrylate monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, behenyl (meth)acrylate, phenyl (meth)acrylate, isooctyl (meth)acrylate, isodecyl (meth)acrylate, cyclohexyl (meth)acrylate, and benzyl methacrylate; aromatic hydrocarbon vinyl monomers such as styrene and 4-hydroxystyrene; vinyl ether monomers such as tert-butyl vinyl ether and cyclohexyl vinyl ether; and vinylidene monomers such as 1,1-dichloroethylene and 1,1-difluoroethylene.

[0183] In addition, "(meth)acrylate" is a general term for acrylate and methacrylate.

[0184] As the polymer (1), a synthetic polymer or a commercially available product may be used.

[0185] 《Polymer (2)》

[0186] The polymer (2) is a fluorine-containing polymer having an aliphatic ring in its main chain.

[0187] The term "fluorinated polymer having an aliphatic ring in the main chain" means that the fluorinated polymer contains a unit having an aliphatic ring structure, and at least one of the carbon atoms constituting the aliphatic ring is a carbon atom constituting the main chain. The aliphatic ring may also be a ring having a hetero atom such as an oxygen atom.

[0188] The "main chain" of a polymer refers to a chain of carbon atoms derived from two carbon atoms constituting a polymerizable double bond in a polymer of a monoolefin having a polymerizable double bond.

[0189] Furthermore, it refers to a chain of carbon atoms derived from four carbon atoms constituting two polymerizable double bonds in a cyclopolymerized diene.

[0190] Furthermore, it also refers to a chain of carbon atoms derived from the above two carbon atoms of the monoolefin and the above four carbon atoms of the diene in a copolymer of a monoolefin and a cyclopolymerizable diene.

[0191] When the monomer of the polymer "having an aliphatic ring in the main chain" is a monoene having an aliphatic ring, one of the monoenes is a monoene having a structure in which one carbon atom constituting the ring skeleton of the aliphatic ring and one carbon atom outside the aliphatic ring are carbon atoms constituting a polymerizable double bond. The main chain of the polymer of such a monoene contains two carbon atoms constituting a polymerizable double bond, one of which is a carbon atom constituting the ring skeleton of the aliphatic ring.

[0192] Another type of monoolefin having an aliphatic ring is a monoolefin having a structure in which two adjacent carbon atoms constituting the ring skeleton are carbon atoms constituting a polymerizable double bond. The main chain of the polymer of this monoolefin contains two carbon atoms constituting a polymerizable double bond, and these two carbon atoms are carbon atoms constituting the ring skeleton of the aliphatic ring.

[0193] Furthermore, when the monomer of the polymer "having an aliphatic ring in the main chain" is a diene capable of cyclopolymerization, one carbon atom in each of the four carbon atoms in the two polymerizable double bonds of the diene is bonded to each other by cyclopolymerization to form an aliphatic ring, and the atomic bonds of the other two carbon atoms become two atomic bonds of the generated unit, thereby forming a divalent unit having an aliphatic ring. The main chain of such a diene polymer contains four carbon atoms constituting two polymerizable double bonds in the diene.

[0194] The number of atoms constituting the ring skeleton of the aliphatic ring in the polymer (2) is preferably 4 to 7, and particularly preferably 5 to 6. That is, as the aliphatic ring, a 4- to 7-membered ring is preferred, and a 5- to 6-membered ring is particularly preferred. When the atoms constituting the aliphatic ring have a hetero atom, examples of the hetero atom include an oxygen atom and a nitrogen atom, and an oxygen atom is preferred. In addition, the number of hetero atoms constituting the ring is preferably 1 to 3, and more preferably 1 or 2.

[0195] The aliphatic ring may or may not have a substituent. “May have a substituent” means that a substituent may be bonded to an atom constituting the ring skeleton of the aliphatic ring.

[0196] The hydrogen atom bonded to the carbon atom of the aliphatic ring constituting the polymer (2) is preferably substituted with a fluorine atom. In addition, when the aliphatic ring has a substituent, when the substituent has a hydrogen atom bonded to the carbon atom, the hydrogen atom is preferably substituted with a fluorine atom. As the substituent having a fluorine atom, perfluoroalkyl, perfluoroalkoxy, =CF2, etc. can be mentioned.

[0197] The aliphatic ring in the polymer (2) is preferably a perfluoroaliphatic ring (an aliphatic ring in which all hydrogen atoms bonded to carbon atoms including substituents are substituted with fluorine atoms).

[0198] Examples of the polymer (2) include the following polymers (21) and (22).

[0199] Polymer (21): a fluorinated polymer having a unit derived from a cyclic fluorinated monoolefin,

[0200] Polymer (22): A fluorinated polymer having units formed by cyclopolymerization of a cyclopolymerizable fluorinated diene (hereinafter also simply referred to as "fluorinated diene").

[0201] Polymer (21):

[0202] The “fluorinated cyclic monoolefin” is a fluorinated monomer having one polymerizable double bond between carbon atoms constituting an aliphatic ring, or a fluorinated monomer having one polymerizable double bond between a carbon atom constituting an aliphatic ring and a carbon atom outside the aliphatic ring.

[0203] As the fluorinated cyclic monoolefin, the following compound (1) or compound (2) is preferred.

[0204]

[0205] [Wherein, X 1 , X 2 , X 3 , X 4 , Y 1 and Y 2Each is independently a fluorine atom, a perfluoroalkyl group which may contain an etheric oxygen atom (—O—), or a perfluoroalkoxy group which may contain an etheric oxygen atom. 3 and X 4 They may be bonded to each other to form a ring.]

[0206] X 1 , X 2 , X 3 , X 4 , Y 1 and Y 2 The carbon number of the perfluoroalkyl group in is preferably 1 to 7, particularly preferably 1 to 4. As the perfluoroalkyl group, a linear or branched perfluoroalkyl group is preferred, and a linear perfluoroalkyl group is particularly preferred. Specifically, trifluoromethyl, pentafluoroethyl, heptafluoropropyl, etc. are mentioned, and trifluoromethyl is particularly preferred.

[0207] As X 1 , X 2 , X 3 , X 4 , Y 1 and Y 2 The perfluoroalkoxy group in the above-mentioned group may be a group in which an oxygen atom (—O—) is bonded to the above-mentioned perfluoroalkyl group, and a trifluoromethoxy group is particularly preferred.

[0208] In formula (1), X 1 A fluorine atom is preferred.

[0209] X 2 A fluorine atom, a trifluoromethyl group, or a perfluoroalkoxy group having 1 to 4 carbon atoms is preferred, and a fluorine atom or a trifluoromethoxy group is particularly preferred.

[0210] X 3 and X 4 Each independently is preferably a fluorine atom or a perfluoroalkyl group having 1 to 4 carbon atoms, and particularly preferably a fluorine atom or a trifluoromethyl group.

[0211] X 3 and X 4 The number of atoms constituting the ring skeleton of the ring is preferably 4 to 7, particularly preferably 5 to 6.

[0212] Preferred specific examples of the compound (1) include compounds (1-1) to (1-5).

[0213]

[0214] In formula (2), Y 1 and Y 2 Each independently is preferably a fluorine atom, a perfluoroalkyl group having 1 to 4 carbon atoms, or a perfluoroalkoxy group having 1 to 4 carbon atoms, and particularly preferably a fluorine atom or a trifluoromethyl group.

[0215] Preferred specific examples of the compound (2) include compounds (2-1) and (2-2).

[0216]

[0217] The polymer (21) may be a homopolymer of the aforementioned fluorinated cyclic monoolefin, or a copolymer of other monomers copolymerizable with the fluorinated cyclic monoolefin.

[0218] Among them, the ratio of the units derived from the fluorinated cyclic monoolefin to all the units in the polymer (21) is preferably 20 mol% or more, more preferably 40 mol% or more, further preferably 100 mol%.

[0219] As other monomers copolymerizable with the fluorinated cyclic monoolefin, for example, there can be mentioned fluorinated dienes, monomers having reactive functional groups in the side chains, tetrafluoroethylene, chlorotrifluoroethylene, perfluoro(methyl vinyl ether), etc. In addition, as other monomers copolymerizable with the fluorinated cyclic monoolefin, the above-mentioned "monomer (f1)" and "other monomers copolymerizable with the monomer (f1)" can also be mentioned.

[0220] Examples of the fluorinated diene include the same ones as exemplified in the description of the polymer (22) described later. The polymer obtained by copolymerization of the fluorinated cyclic monoolefin and the fluorinated diene is referred to as polymer (21).

[0221] As the monomer having a reactive functional group in the side chain, there can be mentioned a monomer having a polymerizable double bond and a reactive functional group. As the polymerizable double bond, there can be mentioned CF2=CF-, CF2=CH-, CH2=CF-, CFH=CF-, CFH=CH-, CF2=C-, CF=CF-, etc. As the reactive functional group, there can be mentioned the same substances as the examples given in the description of the polymer (22) described later.

[0222] Polymer (22):

[0223] The "fluorinated diene" is a fluorinated monomer having two polymerizable double bonds and a fluorine atom and capable of cyclopolymerization. The polymerizable double bond is preferably a vinyl group, an allyl group, an acryloyl group, or a methacryloyl group. The fluorinated diene is preferably the following compound (3).

[0224] CF2=CF-Q-CF=CF2 (3).

[0225] In formula (3), Q is a perfluoroalkylene group having 1 to 5 carbon atoms, preferably 1 to 3 carbon atoms, which may contain an etheric oxygen atom and may have a portion of fluorine atoms substituted by halogen atoms other than fluorine atoms and may have a branch. Examples of the halogen atoms other than fluorine atoms include chlorine atoms and bromine atoms.

[0226] Q is preferably a perfluoroalkylene group containing an etheric oxygen atom. In this case, the etheric oxygen atom in the perfluoroalkylene group may be present at one end of the perfluoroalkylene group, at both ends of the perfluoroalkylene group, or between carbon atoms of the perfluoroalkylene group. From the perspective of cyclopolymerization, it is preferred that the etheric oxygen atom be present at one end of the perfluoroalkylene group.

[0227] Specific examples of the compound (3) include the following compounds.

[0228] CF2=CFOCF2CF=CF2,

[0229] CF2=CFOCF(CF3)CF=CF2、

[0230] CF2=CFOCF2CF2CF=CF2,

[0231] CF2=CFOCF2CF(CF3)CF=CF2,

[0232] CF2=CFOCF(CF3)CF2CF=CF2,

[0233] CF2=CFOCFClCF2CF=CF2,

[0234] CF2=CFOCCl2CF2CF=CF2,

[0235] CF2=CFOCF2OCF=CF2,

[0236] CF2=CFOC(CF3)2OCF=CF2、

[0237] CF2=CFOCF2CF(OCF3)CF=CF2,

[0238] CF2=CFCF2CF=CF2,

[0239] CF2=CFCF2CF2CF=CF2,

[0240] CF2=CFCF2OCF2CF=CF2.

[0241] Examples of the unit formed by cyclopolymerization of the compound (3) include the following units (3-1) to (3-4).

[0242]

[0243] The polymer (22) may be a homopolymer of the fluorinated diene or a copolymer of other monomers copolymerizable with the fluorinated diene.

[0244] Examples of other monomers copolymerizable with the fluorine-containing diene include monomers having a reactive functional group in a side chain, tetrafluoroethylene, chlorotrifluoroethylene, and perfluoro(methyl vinyl ether).

[0245] Specific examples of the polymer (22) include a polymer having p units represented by the following formula (3-1-1) obtained by cyclopolymerizing CF2=CFOCF2CF2CF=CF2 (perfluoro(3-butenyl vinyl ether)).

[0246] In addition, perfluoro(3-butenyl vinyl ether) is hereinafter referred to as "BVE".

[0247]

[0248] In formula (3-1-1), p is an integer of 5 to 1,000.

[0249] As p, 10-800 is preferable, and 10-500 is particularly preferable.

[0250] The functional group at the main chain terminal of the polymer (2) is preferably a low-reactive functional group. Examples of the low-reactive functional group include an alkoxycarbonyl group and a trifluoromethyl group.

[0251] As the polymer (2), a synthetic polymer may be used, or a commercially available polymer may be used.

[0252] Specific examples of the polymer (2) include preferably BVE cyclized polymer (manufactured by AGC Corporation: CYTOP (registered trademark)), tetrafluoroethylene / perfluoro(4-methoxy-1,3-dioxole) copolymer (manufactured by Solvay: Hyflon (registered trademark) AD), tetrafluoroethylene / perfluoro(2,2-dimethyl-1,3-dioxole) copolymer (manufactured by Dupont: Teflon (registered trademark) AF), and perfluoro(4-methyl-2-methylene-1,3-dioxolane) polymer (MMD polymer).

[0253] In the present invention, the fluorinated polymer is preferably the polymer (2), more preferably the polymer (22), and particularly preferably a fluorinated polymer represented by the formula (3-1-1) obtained by cyclopolymerizing BVE.

[0254] Furthermore, when the organic semiconductor and the fluorine-containing polymer are co-evaporated, a dopant for the organic semiconductor may also be co-evaporated.

[0255] like Figure 5As shown, it is considered that when the organic semiconductor and the fluorine-containing polymer are co-evaporated, the organic semiconductor and the fluorine-containing polymer are phase-separated on the substrate to form an organic semiconductor domain 51b and a fluorine-containing polymer domain 52b.

[0256] It is believed that the size (diameter) of the fluorine-containing polymer domain 52b falls within a certain numerical range with little fluctuation according to the relationship between the surface energy of the co-evaporation substrate 50 and the surface energy of the fluorine-containing polymer. In other words, it is believed that when the fluorine-containing polymer used is easy to be coated and spread on the surface of the substrate 50, the domain 52b is easy to be widely spread, and when the fluorine-containing polymer is not easy to be coated and spread on the surface of the substrate 50, the diameter of the domain 52b is easy to be reduced.

[0257] like Figure 6 As shown, it is considered that if the co-evaporation is continued, the organic semiconductor 51a evaporated from the evaporation source 51 is more energetically stable than being deposited in the domain 52b, and is therefore deposited in the domain 51b of the organic semiconductor. Similarly, the fluorine-containing polymer 52a evaporated from the evaporation source 52 is more energetically stable than being deposited in the domain 51b, and is therefore deposited in the domain 52b of the fluorine-containing polymer.

[0258] Thus, a domain 51b of an organic semiconductor continuous in the thickness direction of the co-evaporated film and a domain 52b of a fluorinated polymer continuous in the thickness direction of the co-evaporated film are formed. In addition, when the co-evaporated film is observed from the normal direction of the substrate 50, the diameter of the domain 52b does not change significantly in the thickness direction of the co-evaporated film, reflecting the size of the initial domain 52b formed on the surface of the substrate 50.

[0259] The fact that the co-evaporated film 10 undergoes phase separation to form the domain 51 b and the domain 52 b can be confirmed by the following method.

[0260] (Confirmation method)

[0261] After embedding / curing the co-evaporated film with epoxy resin, it was cut with an ultrathin slicer to make ultrathin sections. The ultrathin sections collected on the microgrid were stained with RuO4 and observed with a transmission electron microscope (HT7700 manufactured by Hitachi High-Technologies Corporation) using a TEM. The acceleration voltage during observation was set to 100 kV, and the shooting was set to high-resolution mode.

[0262] Then, if Figure 7 As shown, the substrate 50 on which the organic semiconductor and the fluorine-containing polymer are co-evaporated is immersed in a fluorine-containing solvent 60 . Figure 7 In the process, the substrate 50 is immersed in the fluorine-containing solvent 60 stored in the storage tank 600 .

[0263] The fluorinated solvent 60 used is one that dissolves the fluorinated polymer forming the domains 52b and substantially does not dissolve the organic semiconductor forming the domains 51b. Thus, the domains 52b are dissolved and removed, and a porous membrane 1 consisting only of the domains 51b is obtained.

[0264] It should be noted that "substantially" not dissolving means that the solubility of the organic semiconductor relative to the fluorinated solvent 60 used is extremely low compared to the solubility of the fluorinated polymer relative to the fluorinated solvent 60, and as a result, the domain 51b is basically not dissolved. By using the fluorinated solvent 60 of this nature, the domain 52b can be dissolved without dissolving the domain 51b within the scope of not damaging the inventive effect of the obtained porous membrane 1. In this meaning, the fluorinated solvent 60 can dissolve the organic semiconductor constituting the domain 51b within the scope of not damaging the inventive effect.

[0265] Such a fluorinated solvent 60 is preferably a fluorine-affinity parameter P obtained by the following method: F The solvent is not less than 1. By using such a fluorine-containing solvent 60, the fluorine-containing polymer domain 52b can be dissolved, while the organic semiconductor domain 51b is not substantially dissolved.

[0266] (Fluorophilic parameter P F )

[0267] 30 μL of the fluorinated solvent was dropped into a two-phase system of 3 g of toluene and 3 g of perfluoromethylcyclohexane, mixed, and allowed to stand overnight, and then the fluorinated solvent contained in the toluene and the fluorinated solvent contained in the perfluoromethylcyclohexane were measured by gas chromatography.

[0268] The concentration of the fluorinated solvent in the toluene (unit: mL / L) is defined as M P , let the concentration of the fluorinated solvent in the perfluoromethylcyclohexane (unit: mL / L) be M F When the value obtained by the following formula (A) is taken as the fluorine affinity parameter P F .

[0269] P F =M F / M P …(A)

[0270] Examples of the fluorinated solvent include the following compounds.

[0271] 1,1,1,2,2,3,3,4,4,5,5,6,6-Tridecafluorohexane (AC2000, manufactured by AGC Co., Ltd.) (P F =12)

[0272] 1,1,1,2,2,3,3,4,4,5,5,6,6-Tridecafluorooctane (AC6000, manufactured by AGC Co., Ltd.) (P F =5.6)

[0273] CYTOP CT-SOLV100E (manufactured by AGC Co., Ltd.) (P F =8.2)

[0274] CYTOP CT-SOLV180 (manufactured by AGC Co., Ltd.) (P F =∞)

[0275] HFE7300 (3M) (P F =8.2)

[0276] 1,1,1,2,2,3,4,5,5,5-decafluoropentane (Vertre XF, manufactured by Chemours) F =3.7)

[0277] 1H,1H,2H,2H-Perfluorooctanol(P F =1.1)

[0278] 1,1,2,2-Tetrafluoroethyl-2,2,2-trifluoroethyl ether (AE3000, manufactured by AGC Co., Ltd.) (P F =0.6)

[0279] HCFC-225ca / HCFC-225cb(45 / 55)(P F =0.3)

[0280] Perfluorobenzene (P F =0.3)

[0281] Hexafluoro-2-propanol (P F =0.24)

[0282] 1H,1H,7H-Perfluoroheptanol (P F =0.23)

[0283] 1H,1H,5H-Perfluoropentanol (P F =0.1)

[0284] By dissolving and removing the fluorinated polymer domains 52 b , continuous pores 11 extending continuously in the film thickness direction of the co-deposited film are formed at the locations where the domains 52 b are formed.

[0285] It should be noted that Figure 7In the method, the substrate 50 on which the organic semiconductor and the fluorine-containing polymer are co-deposited is immersed in the fluorine-containing solvent 60, but the method of dissolving and removing the fluorine-containing polymer is not limited thereto. For example, the substrate 50 on which the organic semiconductor and the fluorine-containing polymer are co-deposited may be exposed to the vapor of the fluorine-containing solvent, the fluorine-containing solvent may be spread on the substrate 50 on which the organic semiconductor and the fluorine-containing polymer are co-deposited, or the fluorine-containing solvent may be poured on the substrate 50 on which the organic semiconductor and the fluorine-containing polymer are co-deposited.

[0286] The confirmation that the continuous pores 11 are formed in the membrane after washing can be performed indirectly by measuring that no fluorinated polymer remains on the membrane, in addition to direct observation based on electron micrographs.

[0287] That is, the infrared absorption spectra of the co-deposited film 10 of the organic semiconductor and the fluorine-containing polymer on the substrate 50 before and after cleaning in the fluorine-containing solvent were measured using an infrared spectrophotometer (manufactured by Thermo Fisher Scientific: Nicoletis10). The peak of CF unique to the fluorine-containing polymer, i.e., the wave number 1200 cm-1, was determined before and after cleaning. -1 The change in absorbance.

[0288] 1200cm -1 When the peak intensity of does not change, the domain 52 b of the fluorine-containing polymer remains, and therefore it is determined that the continuous pore 11 is not formed.

[0289] On the other hand, 1200cm -1 When the peak intensity of is reduced, it is judged that the domains 52 b of the fluorine-containing polymer are reduced and the continuous pores 11 are formed.

[0290] The formation of continuous pores 11 in the co-deposited film can also be confirmed by measuring the refractive index after drying the washed film. If the washed film has continuous pores 11, the refractive index of the washed film is lower than that of the organic semiconductor used.

[0291] Next, the fluorinated solvent is removed from the cleaned film. In this step, the fluorinated solvent can be removed by heating, decompression, air supply, and a combination thereof. For example, the fluorinated solvent can be appropriately removed by vacuum drying at a temperature lower than the glass transition temperature of the organic semiconductor used in the co-evaporation. At this time, if the temperature is heated to a temperature above the glass transition temperature of the organic semiconductor (e.g., above 100° C.), there is a concern that the continuous pores 11 will be crushed.

[0292] As described above, the porous membrane 1 can be produced.

[0293] The porous membrane 1 having the above-described structure can provide a membrane formed of an organic semiconductor and having a refractive index lower than that of the organic semiconductor.

[0294] Furthermore, by using the above-described method for producing the porous membrane 1 , it is possible to easily produce a membrane that uses an organic semiconductor as a forming material and has a lower refractive index than the organic semiconductor.

[0295] [Second embodiment]

[0296] Figures 8 to 10 This is an explanatory diagram of a method for producing a porous membrane 2 according to a second embodiment of the present invention. In the following embodiments, components that have already been described are denoted by the same reference numerals and detailed descriptions thereof will be omitted.

[0297] like Figure 8 As shown, in this embodiment, first, a co-evaporated film 10 having a domain 51b of an organic semiconductor and a domain 52b of a fluorinated polymer is formed on a substrate 50. The organic semiconductor constituting the domain 51b is equivalent to the "first organic semiconductor" in the present invention. In addition, the co-evaporated film 10 is equivalent to the "first film" in the present invention.

[0298] Next, an organic semiconductor 53a different from the first organic semiconductor and a fluorine-containing polymer 54a are co-deposited. The organic semiconductor 53a corresponds to the "second organic semiconductor" in the present invention. The organic semiconductor 53a uses a co-depositable material similar to the first organic semiconductor.

[0299] The fluorinated polymer 54a used at this time may be the same as or different from the fluorinated copolymer constituting the domain 52b. In the present embodiment, the fluorinated polymer 54a is the same material as the fluorinated polymer constituting the domain 52b.

[0300] It is believed that if the fluorinated polymer 54a and the organic semiconductor 53a are co-evaporated after the formation of the co-evaporated film 10, the organic semiconductor 53a is more energetically stable than being deposited in the domain 52b, and is therefore deposited in the domain 51b of the organic semiconductor. Similarly, it is believed that the fluorinated polymer 54a is more energetically stable than being deposited in the domain 51b, and is therefore deposited in the domain 52b of the fluorinated polymer.

[0301] Therefore, if Fig. 9 As shown, a co-deposited film 20 having organic semiconductor domains 53b continuous in the film thickness direction of the co-deposited film and fluorine-containing polymer domains 54b continuous in the film thickness direction of the co-deposited film is formed. The co-deposited film 20 corresponds to the "second film" in the present invention.

[0302] The domain 53b is continuous with the domain 51b formed of the first organic semiconductor in the thickness direction of the co-deposited film. The domain 54b is continuous with the domain 52b formed of the fluorine-containing polymer in the thickness direction of the co-deposited film.

[0303] When forming the co-evaporated film 20, the evaporation conditions are set so that the ratio of the fluorinated polymer to the total of the fluorinated polymer and the organic semiconductor in the formed co-evaporated film is 20 to 80 volume %. In the co-evaporated film 10 and the co-evaporated film 20, the ratio of the fluorinated polymer to the total of the fluorinated polymer and the organic semiconductor may be the same or different.

[0304] Then, if Fig.10 As shown, the substrate 50 on which the co-evaporated films 10 and 20 are formed is immersed in a fluorine-containing solvent 60. As the fluorine-containing solvent 60, the same fluorine-containing solvent as that shown in the first embodiment can be used. Thus, the domains 52b and 54b of the fluorine-containing polymer can be dissolved and removed.

[0305] By removing the domains 52 b and 54 b , continuous holes 11 extending continuously in the film thickness direction of the co-evaporated film are formed in the portions where the domains 52 b and 54 b are formed.

[0306] As described above, the porous membrane 2 can be produced.

[0307] The porous membrane 2 having the above-described structure can also provide a membrane formed of an organic semiconductor and having a lower refractive index than the organic semiconductor.

[0308] Furthermore, by using the above-described method for producing the porous membrane 2 , it is also possible to easily produce a membrane that uses an organic semiconductor as a forming material and has a lower refractive index than the organic semiconductor.

[0309] Furthermore, in the method for producing the porous membrane 2 as described above, if the steps of Fig. 9 After forming the co-evaporated film 20 shown in FIG. 1 , an organic semiconductor and a fluorinated polymer are co-evaporated, and three or more co-evaporated films having domains of organic semiconductor and domains of fluorinated polymer as described above can be stacked. From the stacked film thus prepared, Fig.10 As shown, by removing the domains of the fluorinated polymer using a fluorinated solvent, three or more porous membranes can be laminated.

[0310] [Third Embodiment]

[0311] Fig.11 , 12 It is an explanatory diagram of the manufacturing method of the porous membrane 3 which concerns on 3rd Embodiment of this invention.

[0312] like Fig.11 As shown, after forming the porous membrane 1, there may be a step of vapor-depositing the organic semiconductor 55a. The organic semiconductor 55a is deposited on the porous membrane 1, and gradually blocks the openings 11a of the continuous pores 11 of the porous membrane 1. This step is equivalent to the "step of blocking the openings" in the present invention.

[0313] The organic semiconductor 55 a may be the same as or different from the organic semiconductor constituting the porous membrane 1 .

[0314] Therefore, if Fig.12 As shown, a porous membrane 3 having a plurality of through holes 13 extending in the membrane thickness direction is obtained. The through holes 13 are blocked on the side opposite to the substrate 50 .

[0315] It should be noted that, in this embodiment, "blocking the opening" includes: Fig.11 The opening diameter of the opening 11a becomes smaller as shown by the symbol α. That is, by implementing this process, as long as the opening diameter of the opening 11a becomes narrower than that before the implementation, it is considered that the opening is blocked. In this sense, after the process of blocking the opening, the opening 11a may not be completely blocked.

[0316] As described above, the porous membrane 3 can be produced.

[0317] The porous membrane 3 having the above-described structure can provide a membrane formed of an organic semiconductor and having a lower refractive index than the organic semiconductor.

[0318] Furthermore, by using the above-described method for producing the porous membrane 3 , it is possible to easily produce a membrane that uses an organic semiconductor as a forming material and has a lower refractive index than the organic semiconductor.

[0319] [Fourth embodiment]

[0320] Fig.13 1 is a schematic cross-sectional view of an organic optoelectronic element (organic EL element) 100 according to a fourth embodiment of the present invention. The organic EL element 100 has a structure in which a substrate 110, an anode 111, a hole injection layer 112, a hole transport layer 113, a light-emitting layer 114, an electron transport layer 115, an electron injection layer 116, and a cathode 117 are stacked in this order. The organic EL element 100 of this embodiment adopts a top emission method in which light L generated in the light-emitting layer 114 is emitted to the outside via the cathode 117.

[0321] (Substrate)

[0322] The substrate 110 may or may not be light-transmissive. As the forming material of the substrate 110, inorganic substances such as glass, quartz glass, silicon nitride, and organic polymers (resins) such as acrylic resins and polycarbonate resins can be used. In addition, if the insulation of the surface is ensured, a metal material can also be used as the forming material of the substrate 110.

[0323] In addition, the substrate 110 includes various wirings and driving elements which are not shown and are electrically connected to the organic EL elements.

[0324] (anode)

[0325] The anode 111 is formed on the substrate 110 and supplies holes (pores) to the hole transport layer 113. The anode 111 has light reflectivity for reflecting light emitted from the light emitting layer 114.

[0326] As a material for forming the anode 111, a conductive metal oxide such as ITO (Indium Tin Oxide: indium-doped tin oxide) or IZO (Indium Zinc Oxide: indium-doped zinc oxide) can be used. In addition, in order to give light reflectivity to the anode 111, a reflective film formed of a metal material is provided on the substrate 110 side of the anode 111. That is, the anode 111 has a laminated structure of a layer formed of a conductive metal oxide and a reflective film.

[0327] In addition, as a material for forming the anode 111, silver can be used.

[0328] The thickness of the anode 111 is not particularly limited, but is preferably 30 to 300 nm. The thickness of the anode 111 is, for example, 100 nm.

[0329] (Hole Injection Layer)

[0330] The hole injection layer 112 is formed between the anode 111 and the hole transport layer 113. The hole injection layer 112 has a function of facilitating the injection of holes from the anode 111 into the hole transport layer 113. It should be noted that the hole injection layer 112 may not be formed.

[0331] The hole injection layer 112 can be formed using the above-mentioned hole injection material.

[0332] The thickness of the hole injection layer 112 is not particularly limited, but is preferably 1 to 100 nm. The thickness of the hole injection layer 112 is, for example, 5 nm.

[0333] (Hole Transport Layer)

[0334] The hole transport layer 113 is formed on the hole injection layer 112. The hole transport layer 113 has a function of efficiently transporting holes injected from the anode 111 to the light emitting layer 114.

[0335] The hole transport layer 113 can be formed using the above-mentioned hole transport material.

[0336] The absorption coefficient of the hole transport layer 113 in the wavelength range of 450 nm to 800 nm is preferably 5000 cm -1 Less than, more preferably 1000cm -1 Hereinafter, it is particularly preferred that there is no absorption band in the above-mentioned wavelength range.

[0337] The absorption coefficient of each layer constituting the hole transport layer 113 exceeds 5000 cm -1 In the case of , if light passes through a hole transport layer with a thickness of 100nm once, 5% of the light is absorbed when the total amount of light before passing is set to 100%. Inside the organic EL element, due to multiple interferences of light, the loss caused by the absorption of light when passing through the hole transport layer 113 accumulates. Therefore, the absorption of light when passing through the hole transport layer becomes the main factor that greatly reduces the light extraction efficiency. It is extremely important to use a hole transport layer with sufficiently small light absorption so as not to damage the luminous efficiency of the organic EL element. By not damaging the luminous efficiency of the organic EL element, the energy utilization efficiency is improved, and the heat generated by light absorption is suppressed, resulting in a longer element life.

[0338] The thickness of the hole transport layer 113 is not particularly limited, but is preferably 10 nm to 250 nm, and more preferably 20 nm to 150 nm.

[0339] (Luminous layer)

[0340] The light-emitting layer 114 is formed in contact with the hole transport layer 113. In the light-emitting layer 114, holes injected from the anode 111 and electrons injected from the cathode 117 are recombined, and photons are emitted to emit light. The emission wavelength at this time is determined by the material forming the light-emitting layer 114. The light-emitting layer 114 is equivalent to the "active layer" in the present invention.

[0341] As a material for forming the light-emitting layer 114, a known material such as a fluorescent material, a thermally activated delayed fluorescence (TADF) material, or a phosphorescent material can be used.

[0342] The materials for forming the light-emitting layer may be used in combination of two or more kinds, and may be appropriately selected according to the desired light-emitting wavelength.

[0343] Examples of the material for forming the light-emitting layer 114 include the following materials, but the material is not limited to these.

[0344] Luminescent guest materials such as (E)-2-(2-(4-(dimethylamino)phenylvinyl)-6-methyl-4H-pyran-4-ylidene)malononitrile (DCM), 4-(dicyanomethylidene)-2-methyl-6-julonidinyl-9-enyl-4H-pyran (DCM2), rubrene, coumarin 6, Ir(ppy)3, (ppy)2Ir(acac);

[0345] Phosphorescent host materials such as 4-4'-bis(9H-carbazole-9-yl)biphenyl (CBP), 3,3'-bis(9H-carbazole-9-yl)-1,1'-biphenyl (mCPB);

[0346] Fluorescent host materials such as ADN and Alq3;

[0347] Polymer materials such as polyphenylene vinylene (PPV) and MEH-PPV.

[0348] The thickness of the light emitting layer 114 is not particularly limited, but is preferably 10 to 30 nm. The thickness of the light emitting layer 114 is, for example, 15 nm.

[0349] (Electron Transport Layer)

[0350] The electron transport layer 115 is formed in contact with the light emitting layer 114. The electron transport layer 115 has a function of efficiently transporting electrons injected from the cathode 117 to the light emitting layer 114.

[0351] The electron transport layer 115 can be formed using the above-mentioned electron transport material.

[0352] The thickness of the electron transport layer 115 is not particularly limited, but is preferably 30 to 80 nm. The thickness of the electron transport layer 115 is, for example, 60 nm.

[0353] (Electron Injection Layer)

[0354] The electron injection layer 116 is provided between the cathode 117 and the electron transport layer 115. The electron injection layer 116 has a function of facilitating the injection of electrons from the cathode 117 to the electron transport layer 115. As a material for forming the electron injection layer 116, the above-mentioned electron injection materials can be used.

[0355] It should be noted that the electron injection layer 116 may not be formed.

[0356] The thickness of the electron injection layer 116 is not particularly limited, but is preferably 0.5 to 2 nm. The thickness of the electron injection layer 116 is, for example, 1 nm.

[0357] (cathode)

[0358] The cathode 117 is formed in contact with the electron injection layer 116. The cathode 117 has a function of injecting electrons into the electron injection layer 116. As a forming material of the cathode 117, a known material can be used. For example, as a forming material of the cathode 117, a MgAg electrode and an Al electrode can be cited. A buffer layer such as LiF can be formed on the surface of the Al electrode.

[0359] The cathode 117 is a semi-transmissive film that is formed to be thin as a whole to such an extent that it reflects a part of the light emitted from the light-emitting layer 114 and transmits the remaining part.

[0360] The thickness of the cathode 117 is not particularly limited, but is preferably 5 to 30 nm. The thickness of the cathode 117 is, for example, 5 nm.

[0361] (Microcavity structure)

[0362] In the organic EL element 100 of this embodiment, the anode 111 and the cathode 117 constitute an optical resonance structure (microcavity) that causes light to resonate between the anode 111 and the cathode 117. Between the anode 111 and the cathode 117, light generated by the light-emitting layer 114 is repeatedly reflected, and light of a wavelength that matches the optical path length between the anode 111 and the cathode 117 resonates and is amplified. On the other hand, light of a wavelength that does not match the optical path length between the anode 111 and the cathode 117 is attenuated.

[0363] The “optical path length” referred to here is calculated using the wavelength of desired light emitted to the outside of the element and the refractive index of each layer at the wavelength of the desired light.

[0364] The optical path length between the anode 111 and the cathode 117 is set to, for example, an integral multiple of the central wavelength of the light L generated by the light emitting layer 114. In this case, the light L emitted by the light emitting layer 114 is amplified as it approaches the central wavelength, and is attenuated as it moves away from the central wavelength, and is emitted to the outside of the organic EL element 100. In this way, the half-value width of the emission spectrum of the light L emitted from the organic EL element 100 is narrowed, and the color purity is improved.

[0365] The microcavity structure utilizes resonance based on fixed end reflection with the cathode and the anode as the two ends. Therefore, when "the optical path length from the light emitting position to the anode is an integral multiple of 1 / 4 of the wavelength λ of the desired light emitted to the outside of the element" and "the optical path length from the light emitting position to the cathode is an integral multiple of 1 / 4 of the wavelength λ of the desired light emitted to the outside of the element", the desired microcavity structure can be formed.

[0366] The organic EL element 100 of this embodiment uses the above-mentioned porous film in at least one of the hole injection layer 112, the hole transport layer 113, the light emitting layer 114, the electron transport layer 115, and the electron injection layer 116. It should be noted that the hole injection layer 112, the hole transport layer 113, the light emitting layer 114, the electron transport layer 115, and the electron injection layer 116 are sometimes collectively referred to as "organic semiconductor layer" below.

[0367] Therefore, the hole injection layer 112, the hole transport layer 113, the luminescent layer 114, the electron transport layer 115, and the electron injection layer 116 can be made low-refractive, and compared with the case where these layers are not porous films, the light extraction efficiency and the external quantum efficiency can be improved. Thus, compared with the previous organic EL element in which the organic semiconductor layer is not a porous film, the same luminous amount as the previous organic EL element can be obtained with less input power.

[0368] In addition, when the adjacent organic semiconductor layers are all porous films, it is preferred that, during the manufacturing process, as shown in the second embodiment above, a manufacturing method is adopted in which the co-evaporated films corresponding to each organic semiconductor layer are stacked and the fluorinated polymer is removed at one time. Specifically, for example, when the hole injection layer 112 and the hole transport layer 113 are both porous films, it is preferred that the hole injection material and the fluorinated polymer are co-evaporated to form a co-evaporated film (first film), and then the hole transport material and the fluorinated polymer are co-evaporated to form a co-evaporated film (second film), and then the fluorinated polymer contained in the first film and the second film is removed at one time.

[0369] In addition, when the hole transport layer 113 is a porous film, it is preferred that a step of blocking the opening of the continuous hole of the hole transport layer 113 is performed as shown in the third embodiment after the hole transport layer 113 is formed and before the light emitting layer 114 is formed. Thus, when the light emitting layer 114 is formed, a part of the light emitting layer 114 will not enter the continuous hole of the hole transport layer 113, and the part where the charge transfer is easily concentrated in the light emitting layer 114 can be eliminated.

[0370] In addition, when the electron transport layer 115 is a porous film, it is preferred that after the formation of the light-emitting layer 114, when the electron transport layer 115 is formed, only the electron transport material is deposited on the light-emitting layer 114 to form a layer of the electron transport material, and then the electron transport material and the fluorine-containing polymer are co-deposited. In this way, the portion where charge transfer is easily concentrated in the light-emitting layer 114 can be eliminated.

[0371] In the organic EL element 100 having the above-described structure, the organic semiconductor layer is formed as a porous film, so that the external quantum efficiency is improved and the power consumption is reduced.

[0372] [Fifth embodiment]

[0373] Fig.14 is an explanatory diagram of an organic EL element 200 according to a fifth embodiment of the present invention, Fig.13 The corresponding figure.

[0374] The organic EL element 200 has a structure in which a substrate 210, an anode 211, a hole injection layer 112, a hole transport layer 113, a light-emitting layer 114, an electron transport layer 115, an electron injection layer 116, and a cathode 217 are stacked in this order. The organic EL element 200 of this embodiment adopts a bottom emission method in which light L generated by the light-emitting layer 114 is emitted to the outside via the anode 211 and the substrate 210.

[0375] The substrate 210 has light transmittance. As the forming material of the substrate 210, inorganic substances such as glass, quartz glass, silicon nitride, and organic polymers (resins) such as acrylic resins and polycarbonate resins can be used. In addition, if it has light transmittance, a composite material formed by stacking or mixing the above materials can also be used.

[0376] The anode 211 is formed on the substrate 210, and supplies holes to the hole transport layer 113. As a material for forming the anode 211, a light-transmitting conductive metal oxide such as ITO or IZO can be used.

[0377] The cathode 217 is formed in contact with the electron injection layer 116. The cathode 217 has a function of reflecting the light L isotropically emitted from the light emitting layer 114 and directing it toward the anode 211.

[0378] The thickness of the cathode 217 is not particularly limited, but is preferably 30 to 300 nm. The thickness of the cathode 217 is, for example, 100 nm.

[0379] In the organic EL element 200 having such a structure, similarly to the organic EL element 100 shown in the fourth embodiment, the above-mentioned porous film is used in at least one of the hole injection layer 112, the hole transport layer 113, the light emitting layer 114, the electron transport layer 115, and the electron injection layer 116. This can improve the light extraction efficiency.

[0380] In the organic EL element 200 having the above-described structure, the organic semiconductor layer is formed as a porous film, so that the external quantum efficiency is improved and the power consumption is reduced.

[0381] It should be noted that a wavelength conversion layer including quantum dots may be disposed in the light emission direction in the organic EL element 100 or the organic EL element 200. By having such a wavelength conversion layer, the color purity of the emitted light can be improved.

[0382] In the organic EL element 100 or the organic EL 200, quantum dots can be used as a material for forming the light-emitting layer 114. Quantum dots refer to nanoscale semiconductor crystals having unique optical properties that follow quantum mechanics. Quantum dots are usually single crystal particles with a diameter of 2 to 10 nm. For quantum dots, the band gap changes depending on the crystal size (= particle size), so by adjusting the particle size, the band gap can be adjusted to obtain the desired light emission wavelength.

[0383] As quantum dots, colloidal quantum dots that can be dispersed in a solution may also be used. Such colloidal quantum dots can be formed into a film using a common wet coating technique.

[0384] The type of quantum dots is not particularly limited, and perovskite quantum dots, carbon-based quantum dots, alloy-type quantum dots, core / shell-type quantum dots, and core-type quantum dots can be used.

[0385] In the above-mentioned embodiment, an organic EL element is described as an example of an organic optoelectronic element. However, the organic optoelectronic element to which the porous film of the present invention is applied is not limited to the organic EL element.

[0386] The organic optoelectronic element of the present invention may also be, for example, an organic semiconductor laser. As the organic semiconductor laser, a known structure may be used. By making the organic semiconductor layer (at least one of the hole injection layer, the hole transport layer, the electron injection layer, and the electron transport layer) possessed by the organic semiconductor laser adopt the above-mentioned porous film, an organic semiconductor laser with improved external quantum efficiency is obtained.

[0387] In addition, the organic optoelectronic element of the present invention may also be a light receiving element such as a photosensor, a solar cell, etc. As photosensors and solar cells, a known structure can be used in which holes and electrons generated in an active layer (light receiving layer) according to the intensity of light received by the active layer are transferred to a cathode and an anode via an organic semiconductor layer.

[0388] By using the above-mentioned porous film as the active layer of the optical sensor and the solar cell, the internal reflection of the light received inside can be suppressed, and the amount of light reaching the active layer can be increased. Furthermore, at least one layer among the hole injection layer, the hole transport layer, the electron injection layer, the active layer, and the electron transport layer can be used as the above-mentioned porous film.

[0389] This provides a photosensor with improved detection performance and a solar cell with improved power generation efficiency.

[0390] Above, the suitable embodiment of the present invention is described with reference to the accompanying drawings, but it is needless to say that the present invention is not limited to the examples. The shapes and combinations of the components shown in the above examples are examples, and various changes can be made based on design requirements within the scope of the main purpose of the present invention.

[0391] Example

[0392] Hereinafter, the present invention will be described by way of examples, but the present invention is not limited to these examples.

[0393] In this embodiment, evaluation was performed by the following methods.

[0394] "Method for determining the refractive index of fluorinated polymers"

[0395] The refractive index of the fluorine-containing polymer is a value measured in accordance with JIS K7142.

[0396] "Method for determining weight average molecular weight (Mw), number average molecular weight (Mn) and polydispersity (Mw / Mn) of fluorinated polymers"

[0397] The weight average molecular weight of the fluorinated polymer was determined using gel permeation chromatography (GPC). First, a PMMA standard sample with a known molecular weight was measured using GPC, and a calibration curve was prepared based on the dissolution time and molecular weight of the peak. Next, the fluorinated polymer was measured, and the weight average molecular weight (Mw) and number average molecular weight (Mn) were calculated based on the calibration curve. The polydispersity (Mw / Mn) was calculated based on Mw and Mn. A mixed solvent of 1,1,1,2,3,4,4,5,5,5-decafluoro-3-methoxy-2-(trifluoromethyl)pentane / hexafluoroisopropanol (85 / 15 by volume) was used as the mobile phase solvent.

[0398] "Method for determining the intrinsic viscosity [η] of fluorinated polymers"

[0399] The intrinsic viscosity [η] of the fluorinated polymer was measured at a measurement temperature of 30° C. using ASAHIKLIN (registered trademark) AC2000 (manufactured by AGC) as a solvent and using an Ubbelohde type viscometer (manufactured by Shibata Scientific Co., Ltd.: Viscometer Ubbelohde).

[0400] "Determination of vapor pressure and evaporation rate of fluorinated polymers"

[0401] The evaporation rate and saturated vapor pressure below 340°C were measured using a vacuum differential thermal balance (VPE-9000 manufactured by ADVANCE RIKO, Inc.). 50 mg of the fluorinated polymer was placed in a sample cell with an inner diameter of 7 mm and the sample was placed in a 1×10 -3 Pa, the temperature was raised at 2°C per minute, and the evaporation rate (g / m) at each temperature below 340°C was measured. 2 · seconds. The saturated vapor pressure is calculated using the evaporation rate and molecular weight.

[0402] "Method for determining the threshold temperature of fluorinated polymers"

[0403] The evaporation rate measured by the above method was reduced from less than 0.1 g / (m 2 ·seconds) becomes 0.1g / (m 2 The boundary temperature above 100 0.1 0.1 0.2 0.4 0.6 0.8 0.9 0.1 0.2 0.4 ...4 0.8 0.9 0.1 0.4 0.

[0404] "Method for determining whether organic semiconductors can be vapor deposited"

[0405] The measurement was performed using a vacuum differential thermal balance (VPE-9000 manufactured by ADVANCE RIKO, Inc.). 50 mg of the organic semiconductor was placed in a sample cell with an inner diameter of 7 mm and the measurement was performed at 1×10 -3~1×10 -4 The weight loss rate (%) of the organic semiconductor when the temperature is increased by 2°C per minute to 500°C under a vacuum degree of 1.5 Pa, and the temperature (T d50 ).

[0406] Next, using a thermogravimetric differential thermal analyzer (manufactured by Hitachi High-Tech Science Corporation: STA7200), the weight loss rate of the organic semiconductor when the temperature was increased at 10°C per minute to 450°C was measured under a nitrogen flow to determine T d50 The weight loss rate.

[0407] T d50 When the weight loss rate under normal pressure is less than 1%, it is judged that the T under reduced pressure d50 The reason for the weight loss is not due to thermal decomposition but evaporation. It is considered that such an organic semiconductor is not decomposed by heating during vapor deposition, that is, it is a material suitable for vapor deposition.

[0408] On the other hand, T d50 If the weight loss rate under normal pressure exceeds 1%, it is judged that the T under reduced pressure d50 The reason for the weight loss is thermal decomposition. It is believed that such an organic semiconductor will decompose due to heating during vapor deposition and is therefore not suitable for vapor deposition.

[0409] "Method for determining porosity"

[0410] The infrared absorption spectrum of the co-deposited film of the organic semiconductor and the fluorinated polymer formed on the silicon substrate before and after cleaning with a fluorinated solvent was measured by an infrared spectrophotometer (Nicoleti S10 manufactured by Thermo Fisher Scientific) to evaluate the peak derived from CF unique to the fluorinated polymer, i.e., the peak at wave number 1200 cm -1 The change in absorbance at 1200 cm -1 When the peak intensity did not change, it was recorded as not being able to be made porous (×), and when the peak intensity was reduced and could not be confirmed, it was recorded as being able to be made porous (○).

[0411] "Method for confirming the phase separation structure of co-evaporated films"

[0412] After embedding / curing the co-evaporated film sample of the organic semiconductor and the fluorine-containing polymer formed on the COP film with epoxy resin, it was cut with an ultrathin slicer to make ultrathin sections. The ultrathin sections collected on the micronet were stained with RuO4 and provided for TEM observation. TEM observation was performed using HT7700 manufactured by Hitachi High-Technologies Corporation, the acceleration voltage during observation was set to 100 kV, and the shooting was set to high-resolution mode.

[0413] "Method for confirming vertical orientation of porous films"

[0414] The porous membrane sample formed on the silicon substrate was evaluated by GI-SAXS measurement. The measurement was carried out using the BL-6A of the High Energy Accelerator Research Institute. The wavelength of the incident X-ray was set to The incident angle was set to 0.16°, the detector was set to PILATUS3 1M, and the camera length was set to 2.5 m.

[0415] "Method for measuring d value (interplanar spacing) of porous membrane"

[0416] The cluster structure of the porous membrane sample formed on the COP film was evaluated by small angle X-ray scattering (SAXS). The incident X-ray was used at Aichi synchrotron BL8S3 with a wavelength of (8.2keV), the beam size was set to about 850μm×280μm, the camera length was set to 1121.52mm, the detector used R-AXISIV (imaging plate), and the exposure time was set to 60 seconds. For data processing, the two-dimensional data was processed by ring averaging using Fit 2D software, and after one-dimensionalization, background correction, transmittance correction, and air scattering correction were performed during IP reading. For sample thickness correction, it was omitted due to low accuracy and uneven locations.

[0417] "Method for measuring film thickness and refractive index of porous films and organic semiconductor films"

[0418] Using a multi-incident angle spectroscopic ellipsometer (JA Woollam: M-2000U), the film on the silicon substrate was measured by changing the incident angle of light by 5 degrees at a time within the range of 45 to 75 degrees. At each angle, Ψ and Δ, which are ellipsometric parameters, were measured at intervals of about 1.6 nm in the range of wavelengths of 450 to 800 nm. Using the aforementioned measurement data, the dielectric constant of the organic semiconductor was fitted and analyzed using the Cauchy model to obtain the refractive index and film thickness of the porous film and the organic semiconductor film for light of a wavelength of 600 nm.

[0419] "Calculation method of porosity of porous membrane"

[0420] As a film formed of an organic semiconductor and air, the porosity of the porous film is calculated by the following formula. It should be noted that the refractive index of air (n a ) is 1, and the refractive indexes of the organic semiconductor and the porous film are the values ​​obtained by the above-mentioned method.

[0421] Porosity (%) = (n p -n o ) / (n a -no )×100

[0422] n p : Refractive index of porous membrane

[0423] n o : Refractive index of organic semiconductor

[0424] n a : Refractive index of air

[0425] "Evaluation method of JV characteristics of electrical conductivity evaluation element"

[0426] A source meter (Keithley (registered trademark) 2401 manufactured by Keithley) was used to measure the current flowing in the conductivity evaluation element per unit voltage while applying voltage with the ITO (indium tin oxide) side as an anode and the aluminum side as a cathode.

[0427] "Method for verifying the light extraction efficiency of organic EL elements"

[0428] 《Verification of effects based on optical calculations》

[0429] In order to verify the effect of improving the light extraction efficiency by making the organic semiconductor layer constituting the organic EL element nanoporous and having a low refractive index, simulation was performed using Setfos4.6 (manufactured by Cyber ​​Net Inc.).

[0430] [Synthesis example 1]

[0431] Weigh 30 g of perfluoro(3-butenyl vinyl ether) (BVE), 30 g of 1,1,1,2,2,3,3,4,4,5,5,6,6-tridecafluorohexane (1H-PFH), 0.5 g of methanol and 0.44 g of diisopropyl peroxydicarbonate (IPP) and place them in a glass reactor with an internal volume of 50 ml. After replacing the inside of the container with high-purity nitrogen, polymerization is carried out at 40°C for 24 hours. The obtained solution is desolvated under the conditions of 666 Pa (absolute pressure) and 50°C to obtain 28 g of fluorinated polymer. The intrinsic viscosity [η] of the obtained fluorinated polymer is 0.04 dl / g.

[0432] Next, the obtained fluorinated polymer was heated in an oven at 300° C. and then treated by the method described in paragraph

[0040] of JP-A-11-152310 to replace the unstable terminal group with a -CF3 group using fluorine gas to obtain fluorinated polymer A.

[0433] The obtained fluoropolymer A had a refractive index of 1.34 for light of wavelength 600 nm and an intrinsic viscosity [η] of 0.04 dl / g. The Mw of the fluoropolymer A was 9000, the Mn was 6000, the Mw / Mn was 1.5, and the saturated vapor pressure at 300°C was 1×10 -3 The evaporation rate at the reduced pressure of 0.002 Pa and 300 ° C is 1×10 -3 Pa under reduced pressure is 0.08g / (m 2 · seconds), in 1×10 -3 The evaporation rate of Pa under reduced pressure exceeds 0.1 g / (m 2 · seconds) is 320°C.

[0434] [Synthesis example 2]

[0435] 2 g of perfluoro(4-methyl-2-methylene-1,3-dioxolane) (MMD), 6 g of 1H-PFH, 0.4 g of methanol and 0.2 g of IPP were weighed and placed in a glass reactor with an internal volume of 50 ml. After replacing the inside of the container with high-purity nitrogen, polymerization was carried out at 40°C for 24 hours. The obtained solution was desolvated under the conditions of 666 Pa (absolute pressure) and 50°C to obtain 1 g of polymer.

[0436] Next, the obtained polymer was heated in an oven at 300° C., immersed in methanol, and heated in an oven at 75° C. for 20 hours, thereby replacing the unstable terminal groups with methyl ester groups, and thus a fluorinated polymer B was obtained.

[0437] The obtained fluorinated polymer B had a refractive index of 1.33 for light with a wavelength of 600 nm, a Mw of 11300, a Mn of 9300, a Mw / Mn of 1.2, and a saturated vapor pressure of 1×10 -3 The evaporation rate at the reduced pressure of 0.007 Pa and 300 ° C is 1×10 -3 Pa under reduced pressure is 0.10g / (m 2 · seconds), in 1×10 -3 The evaporation rate of Pa under reduced pressure exceeds 0.1 g / (m 2 The threshold temperature of the 200 Hz to 400 Hz periodic scan is 290°C.

[0438] [Synthesis example 3]

[0439] A jacketed polymerization tank (made of stainless steel) with an internal volume of 1.351 L was degassed, and 617 g of AE-3000 (made by Asahi Glass Co., Ltd.), 145 g of perfluoropropoxyethylene (PPVE), 106 g of tetrafluoroethylene (TFE), and 35.9 g of methanol were weighed and put into the polymerization tank. The temperature was maintained at 60°C, and 18.9 mL of a 7.77 mass% solution of tert-butyl peroxypivalate (PBPV) (solvent: AE-3000) was added to start the polymerization. During the polymerization, TFE was introduced into the polymerization tank, and the polymerization pressure was maintained at 1.04 MPa in a gauge pressure. It should be noted that the atmospheric pressure is 133.322 Pa.

[0440] As the polymerization proceeded, the polymerization pressure decreased, so TFE was continuously introduced to keep the polymerization pressure substantially constant. The polymerization was terminated when the amount of TFE introduced reached 121 g, to obtain a fluorinated copolymer X. The composition of the obtained polymer was PPVE unit:TFE unit=4:96 (mol %).

[0441] Next, the obtained polymer was heated in an oven at 330° C., immersed in methanol, and heated in an oven at 75° C. for 40 hours, thereby replacing the unstable terminal groups with methyl ester groups, thereby obtaining a fluorinated polymer C.

[0442] The obtained fluorinated polymer C has a refractive index of 1.34 for light with a wavelength of 600 nm and an evaporation rate of 1×10 -3 Pa under reduced pressure is 0.10g / (m 2 · seconds), in 1×10 -3 The evaporation rate of Pa under reduced pressure exceeds 0.1 g / (m 2 · seconds) is 300°C.

[0443] [Determination of whether organic semiconductors can be deposited]

[0444] The organic semiconductors shown in Table 1 below were evaluated for vapor deposition capability by the above method.

[0445] In the judgment column, T d50 If the weight loss rate under normal pressure is less than 1% and the vapor deposition is possible, it is recorded as "0"; T d50 When the weight loss rate under normal pressure exceeded 1% and vapor deposition was impossible, it was recorded as "×".

[0446] [Table 1]

[0447]

[0448] As shown in Table 1, for each organic semiconductor with a molecular weight of 300 to 1000, T d50The weight loss rate under normal pressure is small, which can be judged that it does not decompose under the vapor deposition conditions and can be vapor deposited.

[0449] On the other hand, the T of P3HT with a molecular weight of 54,000 d50 If the weight loss rate under normal pressure exceeds 1%, it can be judged that decomposition will occur under the vapor deposition conditions and vapor deposition cannot be performed.

[0450] <Evaluation 1: Evaluation of porous film>

[0451] [Example 1-1]

[0452] A silicon substrate cut into about 2.5 cm square and a COP film (ZF16, 100 μm thick, manufactured by Zeon Corporation, Japan) were placed in a vacuum deposition machine at a pressure of 10 -4 2TNATA and the fluorinated polymer A were co-evaporated under a reduced pressure of not more than 10 Pa to obtain a co-evaporated film having a film thickness of about 100 nm.

[0453] The deposition was adjusted so that the volume ratio of 2TNATA to the fluorine-containing polymer in the co-deposited film was 80:20. The total deposition rate of the two materials was 0.2 nm / sec.

[0454] The obtained co-evaporated film was placed on an AC2000 (AGC Co., Ltd., P F = 12) for 5 minutes, followed by vacuum drying at room temperature for 5 minutes to obtain a porous membrane of Example 1-1.

[0455] [Example 1-2]

[0456] A porous membrane of Example 1-2 was obtained in the same manner as in Example 1-1 except that the volume ratio of 2TNATA to the fluorinated polymer in the co-deposited film was adjusted to 50:50.

[0457] In the co-evaporated film produced in Example 1-2, it was confirmed that 2TNATA and the fluorinated polymer A were phase-separated by the above-mentioned method. Fig.15 This is a cross-sectional TEM image of the co-evaporated film produced in Example 1-2. Fig.15 The symbol A shown is a co-evaporated film. As shown in the figure, it can be confirmed that a phase separation structure oriented in the film thickness direction is formed in the co-evaporated film.

[0458] [Example 1-3]

[0459] A porous film of Example 1-3 was obtained in the same manner as in Example 1-1 except that the volume ratio of 2TNATA to the fluorinated polymer in the co-deposited film was adjusted to 20:80.

[0460] [Example 1-4]

[0461] A co-vapor-deposited film was obtained in the same manner as in Example 1-1 except that the volume ratio of 2TNATA to the fluorinated polymer was adjusted to 60:40.

[0462] The obtained co-evaporated film was exposed to reflux vapor of AC2000 to remove the fluorinated polymer, thereby obtaining the porous film of Example 1-4.

[0463] [Example 1-5]

[0464] A co-deposited film was obtained in the same manner as in Example 1-1 except that the volume ratio of 2TNATA to the fluorinated polymer was adjusted to 40:60.

[0465] The obtained co-evaporated film was spin-cleaned at 200 rpm for 60 seconds using AC2000 and then spin-dried at 2000 rpm for 30 seconds to obtain a porous film of Example 1-5.

[0466] [Example 1-6]

[0467] The fluorinated solvent in which the co-evaporated film was immersed was HFE7300 (manufactured by 3M Co., Ltd., P F =8.2), a porous membrane of Example 1-6 was obtained in the same manner as in Example 1-2 except for the above.

[0468] [Example 1-7]

[0469] A porous membrane of Example 1-7 was obtained in the same manner as in Example 1-2, except that α-NPD was used instead of 2TNATA and fluorinated polymer B was used instead of fluorinated polymer A.

[0470] [Example 1-8]

[0471] A porous membrane of Example 1-8 was obtained in the same manner as in Example 1-2 except that HT211 was used instead of 2TNATA.

[0472] [Example 1-9]

[0473] A porous membrane of Example 1-9 was obtained in the same manner as in Example 1-2 except that Tris-PCz was used instead of 2TNATA.

[0474] [Example 1-10]

[0475] A porous membrane of Example 1-10 was obtained in the same manner as in Example 1-2 except that TPBi was used instead of 2TNATA.

[0476] [Example 1-11]

[0477] A porous membrane of Example 1-11 was obtained in the same manner as in Example 1-2 except that mCBP was used instead of 2TNATA.

[0478] [Example 1-12]

[0479] The silicon substrate cut into about 2.5 cm square was placed in a vacuum deposition machine at a pressure of 10 -4 2TNATA was vapor-deposited under reduced pressure of not more than 100 Å (the volume ratio of 2TNATA to the fluorinated polymer was 100:0) to obtain a film of Example 1-12 having a film thickness of about 100 nm.

[0480] The deposition rate was set to 0.1 nm / sec.

[0481] [Example 1-13]

[0482] Except having used the fluorinated polymer C instead of the fluorinated polymer A, it carried out similarly to Example 1-2, and obtained the film of Example 1-13.

[0483] [Example 1-14]

[0484] The same operation as in Example 1-2 was carried out except that P3HT was used instead of 2TNATA to attempt to produce a porous film. However, P3HT did not achieve the desired deposition rate and was thermally decomposed on the deposition boat, so that no co-deposited film could be obtained.

[0485] Among the above-mentioned Examples 1-1 to 1-14, Examples 1-1 to 1-11 correspond to working examples, and Examples 1-12 to 1-14 correspond to comparative examples.

[0486] The results of evaluation of Examples 1-1 to 1-14 by the above-mentioned method are shown in Tables 2 and 3. In addition, Table 4 shows the refractive index of the organic semiconductor used in Examples 1-1 to 1-14.

[0487] In the Porosity Determination column of Table 3, the above determination method was used to confirm that 1200 cm -1 Absorbance change, 1200cm -1 When the peak intensity did not change, it was considered that the porous structure could not be made and recorded as "×". When the peak intensity decreased and could not be confirmed, it was considered that the porous structure could be made and recorded as "0".

[0488] [Table 2]

[0489]

[0490] [Table 3]

[0491]

[0492] [Table 4]

[0493] Refractive index(@600nm) 2TNATA 1.81 α-NPD 1.78 HT211 1.83 Tris-PCz 1.88 TPB 1.73 mCBP 1.77

[0494] For the evaluation results, in Example 1-13, 1200 cm -1 No change was observed in the peak intensity, confirming that the porous structure could not be made porous.

[0495] On the other hand, in Examples 1-1 to 1-11, 1200 cm -1 The peak intensity of was reduced and the peak could not be confirmed, confirming that the porous membranes of Examples 1-1 to 1-11 could be made porous. In addition, it was confirmed that the porous membranes of Examples 1-1 to 1-11 could be made lower in refractive index than the refractive index of the organic semiconductor used.

[0496] The porous membranes of Examples 1-4 to 1-9 and 1-11 were produced by the same production method as that of Examples 1-1 to 1-3 and 1-10, and through-holes oriented in a direction perpendicular to the substrate were formed.

[0497] <Evaluation 2: Evaluation of electrical conductivity of porous film>

[0498] [Example 2-1]

[0499] A glass substrate having an ITO (indium tin oxide) film formed in a strip shape with a width of 2 mm was ultrasonically cleaned using a neutral detergent, acetone, and isopropyl alcohol in sequence, and then boiled in isopropyl alcohol for cleaning. The attached matter on the surface of the ITO film was then removed by ozone treatment.

[0500] The cleaned substrate is placed in a vacuum evaporator at a pressure of 10 -4 2TNATA and the fluorinated polymer A were co-evaporated under a reduced pressure of not more than 10 Pa to obtain a co-evaporated film having a film thickness of about 100 nm.

[0501] During the deposition, the volume ratio of 2TNATA to the fluorinated polymer in the co-deposited film was adjusted to 50:50. The total deposition rate of the two materials was set to 0.2 nm / sec.

[0502] The obtained co-evaporated film was immersed in AC2000 together with the glass substrate in a glove box for 5 minutes, and then vacuum dried at room temperature for 5 minutes to obtain a porous film.

[0503] Next, at a pressure of 10 -4 2TNATA was stacked on the porous membrane at a thickness of 20 nm under a reduced pressure of Pa or less to block the openings of the continuous pores in the porous membrane.

[0504] Next, aluminum was vapor-deposited in a strip shape having a width of 2 mm on the surface of the porous film whose openings were blocked so as to be perpendicular to the ITO film in a plan view, thereby obtaining an element for evaluating conductivity of Example 2-1.

[0505] The area of ​​the 2 mm×2 mm region where the ITO film and the aluminum film intersect is the device area.

[0506] [Example 2-2]

[0507] A porous membrane with blocked openings was obtained in the same manner as in Example 2-1 except that TPBi was used instead of 2TNATA as the organic semiconductor.

[0508] Next, on the surface of the porous membrane whose openings are blocked, a pressure of 10 -4 LiF was deposited in a thickness of 0.8 nm at a deposition rate of 0.02 nm / s under a reduced pressure of less than Pa.

[0509] Next, an aluminum film was vapor-deposited in the same manner as in Example 2-1, thereby obtaining a conductivity evaluation element of Example 2-2.

[0510] [Example 2-3]

[0511] An element for evaluating conductivity of Example 2-3 was obtained in the same manner as in Example 2-1 except that NDP-9 (purchased from Analytical Engineering Studio Co., Ltd.) was further co-deposited at a deposition rate of 0.01 nm / s during co-deposition of 2TNATA and fluorinated polymer A.

[0512] [Example 2-4]

[0513] The substrate cleaned in the same manner as in Example 2-1 was placed in a vacuum deposition machine at a pressure of 10 -4 2TNATA was vapor-deposited under reduced pressure of 1.3 Å or less Pa to obtain a vapor-deposited film of an organic semiconductor having a film thickness of about 100 nm. The vapor deposition rate was set to 0.1 nm / sec.

[0514] On the surface of the obtained vapor-deposited film, aluminum was vapor-deposited in a strip shape having a width of 2 mm so as to be perpendicular to the ITO film in a plan view, thereby obtaining an element for evaluating conductivity of Example 2-4.

[0515] [Example 2-5]

[0516] A film of an organic semiconductor was obtained in the same manner as in Example 2-4 except that TPBi was used instead of 2TNATA as the organic semiconductor.

[0517] On the surface of the obtained vapor-deposited film, at a pressure of 10 -4 Under reduced pressure of less than Pa, LiF was deposited at a deposition rate of 0.02 nm / s to a thickness of 0.8 nm.

[0518] Next, an aluminum film was vapor-deposited in the same manner as in Example 2-1 to obtain an element for evaluating conductivity of Example 2-5.

[0519] In the above-mentioned Examples 2-1 to 2-5, Examples 2-1 to 2-3 correspond to working examples, and Examples 2-4 and 2-5 correspond to comparative examples.

[0520] Table 5 shows the results of evaluation of Examples 2-1 to 2-5 by the above-mentioned method.

[0521] [Table 5]

[0522]

[0523] The evaluation results show that the electrical conductivity of the vapor-deposited films of Examples 2-1 to 2-3, which are porous films, is not inferior to the electrical conductivity of the vapor-deposited films of Examples 2-4 and 2-5, which do not have voids inside.

[0524] <Evaluation 3: Optical Calculation of Organic EL Element>

[0525] [Examples 3-1~3-10]

[0526] In order to verify the effect of improving the light extraction efficiency by making the organic layers (hole transport layer, light emitting layer, electron transport layer) of the organic EL element nanoporous and having a low refractive index, a simulation was performed by the above method.

[0527] For the analyzed element structure, glass (thickness 1 mm) is used as the substrate, ITO (thickness 100 nm) is used as the anode, 2-TNATA is used as the first hole transport layer, α-NPD is used as the second hole transport layer, the light-emitting layer is a layer containing Ir(ppy)3 as the light-emitting guest and 4,4'-bis(9H-carbazole-9-yl)biphenyl (CBP) as the light-emitting host (thickness 15 nm), TPBi is used as the electron transport layer, and Al (thickness 100 nm) is used as the cathode.

[0528] During simulation, the wavelength of Default Optics Settings is set to 550nm.

[0529] In addition, for the materials constituting each layer, ITO, 2-TNATA, α-NPD, Ir(ppy) 3 The optical data of Al (refractive index, extinction coefficient) used are those in Setfos4.6.11.

[0530] The optical data of TPBi were measured by multi-incident angle spectroscopic ellipsometer (refractive index 1.75 at a wavelength of 550 nm, extinction coefficient 1×10 -5 ).

[0531] The light emitting layer was set as follows.

[0532] Unit: probability

[0533] Distribution: Dlsta

[0534] Position:0.5

[0535] Dipoleorientation: Isotropic

[0536] The film thickness of the electron transport layer and the film thickness of the first hole transport layer were scanned at 10 nm intervals within the range of 10 to 100 nm, and the condition at which the light extraction efficiency was maximized was calculated.

[0537] For Examples 3-1 to 3-10, the film thicknesses of the first hole transport layer, the second hole transport layer, the light emitting layer, and the electron transport layer were set as shown in Table 6 below. In addition, whether a porous film was used for the first hole transport layer, the light emitting layer, and the electron transport layer was set. In the case where a porous film was used in each example, "0" was recorded in the column of the porous film in Table 6.

[0538] [Table 6]

[0539]

[0540] When the first hole transport layer is a porous film, the refractive index at a wavelength of 550 nm is 1.45 and the extinction coefficient is 4.8×10 -9 .

[0541] When the light-emitting layer is a porous film, the refractive index at a wavelength of 550 nm is 1.45 and the extinction coefficient is 4.8×10 -9 .

[0542] When the electron transport layer is a porous film, the refractive index at a wavelength of 550 nm is 1.39 and the extinction coefficient is 2.0×10 -7 .

[0543] In the above-mentioned Examples 3-1 to 3-10, Examples 3-1 to 3-9 correspond to working examples, and Example 3-10 corresponds to a comparative example.

[0544] The evaluation results are shown in Table 7 below.

[0545] [Table 7]

[0546] Light extraction efficiency (OCE) (%) Example 3-1 33.9 Example 3-2 34.1 Example 3-3 46.0 Example 3-4 34.4 Example 3-5 48.7 Example 3-6 40.1 Example 3-7 42.8 Example 3-8 29.2 Example 3-9 29.2 Example 3-10 24.6

[0547] The evaluation results show that Examples 3-1 to 3-9 in which at least one of the hole transport layer, the light emitting layer, and the electron transport layer is a porous film have higher light extraction efficiency than Example 3-10 in which there is no porous film.

[0548] From the above results, it was confirmed that the present invention is useful.

[0549] It should be noted that the entire contents of the specification, claims, abstract, and drawings of Japanese Patent Application No. 2019-194241 filed on October 25, 2019 are cited herein and incorporated as a disclosure of the specification of the present invention.

[0550] Description of Reference Numerals

[0551] 1-3...porous film, 10, 20...co-evaporated film, 11, 13...continuous pores, 11a...opening, 50...substrate, 60...fluorine-containing solvent, 51, 52...evaporation source, 51a, 53a, 55a...organic semiconductor, 51b, 53b...domain (of organic semiconductor), 52a, 54a...fluorine-containing polymer, 52b, 54b...domain (of fluorine-containing polymer), 100, 200...organic EL element (organic optoelectronic element), 110, 210...substrate, 111...anode, 112...hole injection layer, 113...hole transport layer, 114...light-emitting layer, 115...electron transport layer, 116...electron injection layer, 117, 217...cathode, 500...chamber, 600...storage tank.

Claims

1. A method for producing a porous membrane, comprising: a vapor deposition step of co-depositing a fluorine-containing polymer soluble in a fluorine-containing solvent and an organic semiconductor to form a film; and a removing step of removing the fluorine-containing polymer contained in the film from the film, In the vapor deposition step, the ratio of the fluorinated polymer to the total of the fluorinated polymer and the organic semiconductor is 20 to 80% by volume. In the removal step, a fluorinated solvent that dissolves the fluorinated polymer and substantially does not dissolve the organic semiconductor is used, and the fluorinated polymer contained in the film is dissolved in the fluorinated solvent and removed, thereby forming a plurality of continuous pores extending in the film thickness direction of the film.

2. The method for producing a porous membrane according to claim 1, wherein The interplanar spacing d value of the porous film obtained by X-ray scattering method is 5 to 100 nm.

3. The method for producing a porous membrane according to claim 1 or 2, wherein: The porosity of the porous membrane is 20 to 80 volume %.

4. The method for producing a porous membrane according to claim 1 or 2, wherein: The molecular weight of the organic semiconductor is 300-1000.

5. The method for producing a porous membrane according to claim 1 or 2, wherein: In the vapor deposition step, a dopant for the organic semiconductor is co-deposited together with the fluorine-containing polymer and the organic semiconductor.

6. The method for producing a porous membrane according to claim 1 or 2, wherein: The weight average molecular weight of the fluorine-containing polymer is 1,500 to 50,000.

7. The method for producing a porous membrane according to claim 1 or 2, wherein: The threshold temperature of the fluorinated polymer determined under the following conditions is 340° C. or less, Determination conditions: For fluoropolymers, the edge is 1×10 -3 When heating at a temperature of 2°C per minute under a vacuum of Pa, the evaporation rate is reduced from less than 0.1 g / (m 2 ·seconds) becomes 0.1g / (m 2 The boundary temperature above 100 0.1 0.1 0.2 0.4 0.6 0.8 0.9 0.1 0.2 0.4 ...4 0.8 0.9 0.1 0.4 0.

8. The method for producing a porous membrane according to claim 1 or 2, wherein: The fluorine-containing polymer is a perfluoropolymer having an aliphatic ring structure in the main chain.

9. The method for producing a porous membrane according to claim 1 or 2, wherein: The fluorine-containing polymer is a polymer having no aliphatic ring structure in the main chain and having a perfluoroalkyl group in the side chain.

10. The method for producing a porous membrane according to claim 1 or 2, wherein: The fluorine-affinity parameter P of the fluorinated solvent is obtained by the following method F is 1 or more, Fluorine affinity parameter P F : In a two-phase system of 3 g of toluene and 3 g of perfluoromethylcyclohexane, 30 μL of the fluorinated solvent was added dropwise and mixed, and after standing overnight, the fluorinated solvent contained in the toluene and the fluorinated solvent contained in the perfluoromethylcyclohexane were measured by gas chromatography. The concentration of the fluorinated solvent in the toluene is set to M P , the concentration of the fluorinated solvent in the perfluoromethylcyclohexane is set to M F When the value obtained by the following formula (A) is taken as the fluorine affinity parameter P F , wherein the unit of the concentration of the fluorinated solvent is mL / L, P F =M F / M P …(A)。 11. The method for producing a porous membrane according to claim 1 or 2, wherein: In the removing step, the film is immersed in the fluorine-containing solvent.

12. The method for producing a porous membrane according to claim 1 or 2, wherein: In the removing step, the film is exposed to the vapor of the fluorine-containing solvent.

13. The method for producing a porous membrane according to claim 1 or 2, wherein: Using a plurality of said organic semiconductors, In the vapor deposition step, after the fluorinated polymer and the first organic semiconductor are co-deposited to form a first film, the fluorinated polymer and the second organic semiconductor are co-deposited to form a second film. In the removing step, the fluorinated polymer contained in the first film and the fluorinated polymer contained in the second film are removed.

14. The method for producing a porous membrane according to claim 1 or 2, wherein: After the removing step, there is a step of vapor depositing the organic semiconductor to block the openings of the plurality of continuous holes.

Citation Information

Patent Citations

  • Preparation of polymer containing fluorine-containing aliphatic cyclic structure

    JP1999152310A

  • Porous membrane for light-emitting devices

    JP2014508385A

  • Methods for treating hepatitis c

    JP2019194241A

  • Electronic devices containing organic semiconductors

    JP2007536718A